Rapidly accreting the Moon from an extended canonical disk - Brynna G. Downey; Robin M. Canup (Icarus, 2026)

Jaguar Range‐Wide Connectivity: Prioritising Core Areas and Corridors Between and Within Protected Areas and Indigenous Lands - Guilherme Costa Alvarenga; Caroline C. Sartor; Ana Carolina Srbek‐Araujo; Ana Cristina Mendes‐Oliveira; Bart Harmsen; Carlos De Angelo; Carolina Franco Esteves; Claudia Bueno de Campos; Daiana Jeronimo Polli; Diego F. Passos Viana; Diogo Maia Gräbin; Emiliano Donadio; et al. (Global Change Biology, 2026)
Anthropogenic habitat transformation has led to population declines and increasing isolation of populations of many species, particularly top predators, where small and fragmented populations often experience limited dispersal and reduced genetic diversity. Jaguars ( Panthera onca ), for example, have lost half of their historical range and most populations outside the Amazon biome are small, isolated and highly threatened. Here, we assess jaguar population connectivity across the species' range by identifying and ranking core areas and dispersal corridors, including linkages among Protected Areas and Indigenous Lands (hereafter, PAs). We used cumulative resistant kernels and factorial Least‐Cost Paths (fLCP) in two complementary approaches: core area‐based and PA‐based connectivity. We identified 307 core areas for jaguar movement, covering ~7.75 million km 2 (55% of the current range), of which approximately half lies within PAs. The largest and highest‐ranked core area spans ~6.5 million km 2 across four biomes (Amazon, Llanos, Chaco and Pantanal). We identified 176 dispersal corridors connecting core areas, although connectivity was not continuous across the entire range. Northern populations (Mexico and Central America) showed several connectivity gaps, whereas South America displayed a large, highly interconnected network linking the Amazon, Llanos, Chaco, Pantanal, Cerrado, Caatinga, Iberá and the Atlantic Forest's Green Corridor. In contrast, coastal Atlantic Forest patches appeared largely isolated. The PA‐based analysis predicted 507 potential corridors connecting 905 PAs, including potential links absent from the core area model, particularly across Central America and between the Darién Gap, Amazon and coastal Atlantic Forest. The core‐area approach provides a more biologically realistic representation of current connectivity, while the PA‐based approach complements it by identifying pragmatic opportunities for long‐term connectivity conservation. Together, these approaches identify priority areas and regions of uncertainty, providing a spatial framework to guide jaguar conservation and connectivity planning under accelerating global change.

Delivering biologically safe stored water in low-resource settings using in-situ electrochemical activation - Gillian E. Clayton; Robin M.S. Thorn; Bethany G. Fox; Madhusudhan Reddy; Jean-Luc Raharison; Jean Freddy Ranaivoarisoa; Jon Shepherd; Mark D. Steer; Darren M. Reynolds (Journal of Water Process Engineering, 2026)

Corrigendum to ‘Associations of residential environmental factors with kidney function in older adults in the Netherlands: A cross-sectional and longitudinal study’ [Environ. Pollut. 397 (2026) 127917] - Kate H. Liang; Marianne C. Verhaar; Natasja M. van Schoor; Gisela G. Slaats; Robin W.M. Vernooij; Erik J. Timmermans (Environmental Pollution, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Identification of antioxidant and anti-inflammatory compounds in the leaf extracts of Euphorbia neriifolia Linn - Merilin Kakoti; Dibya Jyoti Hazarika; Swati Acharjee; Sristisri Upadhyaya; Rupamoni Thakur; Debajyoti Bhuyan; Robin Chandra Boro; T. G. Devina (Natural Product Research, 2026)

Associations of residential environmental factors with kidney function in older adults in the Netherlands: A cross-sectional and longitudinal study - Kate H. Liang; Marianne C. Verhaar; Natasja M. van Schoor; Gisela G. Slaats; Robin W.M. Vernooij; Erik J. Timmermans (Environmental Pollution, 2026)

Modelling of atmospheric copper, iron, and manganese over Europe - N. Dubois; G. Foret; G. Siour; G. Uzu; F. Amato; J.-M. André; A. Alastuey; L.Y. Alleman; Robin Aujay-Plouzeau; S. Conil; F. Couvidat; A. Ito; et al. (Atmospheric Environment, 2026)

Potential for Manganese Oxide Driven Anaerobic Methane Oxidation in Sediments of a Seasonally Euxinic Coastal Basin - Robin Klomp; Anna J. Wallenius; Niels A. G. M. van Helmond; Wytze K. Lenstra; Olga M. Żygadłowska; Mike S. M. Jetten; Caroline P. Slomp (Estuaries and Coasts, 2026)
Methane (CH 4 ) is a strong greenhouse gas that, in marine sediments, is produced via methanogenesis and removed via oxidation with electron acceptors such as oxygen, sulfate and metal oxides . This study assesses the potential for manganese driven anaerobic oxidation of methane (Mn-AOM) in rapidly accumulating sediments in a seasonally euxinic coastal marine basin (Scharendijke basin, Lake Grevelingen, the Netherlands). Geochemical sediment and porewater profiles demonstrate that, at the study site, Mn oxides are buried in the methanic zone. Sediment incubations amended with 13 C-CH 4 and various Mn forms indicate that the Mn oxide minerals birnessite, pyrolusite and manganite can enhance CH 4 oxidation, whereas ligand bound dissolved Mn(III) does not. This is attributed to either direct Mn-AOM, where Mn oxides act as the electron acceptor, and/or indirect Mn-driven AOM via cryptic sulfur cycling. Results of 16S rRNA gene amplicon sequencing of the incubated sediment point towards a likely role for anaerobic methanotrophic archaea of the clades ANME-2ab and ANME-3 in direct and indirect Mn-driven AOM, respectively. An increase in relative abundance of the methanogen Methanosarcina in several of the incubations suggests that these versatile methanogens benefit from Mn oxide reduction. This study demonstrates potential for Mn-driven AOM in sediments from a eutrophic, seasonally euxinic coastal basin, and expands the range of electron acceptors involved in CH 4 removal in such systems.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Segregation, socioeconomics, and urban design produce spatial bias in community science biodiversity data: A case study in Saint Louis, Missouri, USA - William A. Slatin; Sacha K. Heath; Anahi Aviles Gamboa; Robin B. McDowell; Elora K. Robeck; Elizabeth G. Biro; Solny A. Adalsteinsson (Urban Ecosystems, 2026)
Community science is a powerful tool to understand biodiversity and species richness globally and in urban settings. Community science initiatives deployed as smartphone apps such as iNaturalist are increasingly used by both members of the public and scientists. Previous research shows that socioeconomic factors affect biodiversity patterns and that people of varying ages, racial, and ethnic backgrounds use smartphone applications in different ways; combined, these patterns may produce systematic biases in community science databases. Recently, spatial biases in community science data have been linked to user identity, income, race, or 20th century housing segregation practices. Here we investigate social and environmental factors driving the spatial distribution of iNaturalist data across census tracts in Saint Louis, Missouri, USA. We gathered 11,066 iNaturalist observations and 18 potential predictor variables from 106 U.S. census tracts and built generalized linear models based on a priori hypotheses about the effects of predictor variables. We compared models using Akaike Information Criterion and determined that the best predictors of iNaturalist observations are socioeconomic status, racial and ethnic diversity, relative location to historically residentially segregated areas, and open accessible green space. Metrics that quantify local segregation and inequality are critical to describe the uneven distribution of iNaturalist observations within Saint Louis. Results have significant implications for how researchers incorporate community science data into biodiversity studies, how they interpret spatial trends of community science databases, and how they might strategize future campaigns to advocate for increasing involvement in community science social networks.

Metals exposures and telomere length as a marker of DNA damage among electronic waste workers and a reference group - Mabel Sarpong Duah; Ibrahim Issah; Shirley V. Simpson; Serwaa A. Bawua; Duah Dwomoh; Joseph K. H. Bonney; Shinsaku Inomata; Thomas G. Robins; Niladri Basu; Arima Hiroaki; Julius N. Fobil (Environmental Science and Pollution Research, 2026)

Land-use legacies drive distinct recovery trajectories and persistently shape the taxonomic and functional composition of tree communities - Vanessa de Souza Moreno; Fabio A.R. Matos; Ricardo G. César; Gabriel D. Colleta; Elisa Díaz García; Robin L. Chazdon; Pedro H.S. Brancalion (Forest Ecology and Management, 2026)

Evaluating dementia risk prediction in mild cognitive impairment: an early health technology assessment of the AI-Mind tool - Robin J. Vermeulen; Marcel G. M. Olde Rikkert; Ron Handels; Ira R. J. Hebold Haraldsen; Hanna Renvall; Paolo M. Rossini; Camillo Marra; Fernando Maestú; Maroeska M. Rovers; Tim M. Govers (GeroScience, 2026)
This study aimed to evaluate the potential cost-effectiveness of implementing a prediction tool for estimating mild cognitive impairment (MCI) to dementia conversion risk. A decision-analytic model was developed to compare the costs and effects of current practice for subjects with MCI to a situation in which the risk of dementia is estimated using a prediction tool. Different scenarios in terms of prediction horizons, prediction characteristics (e.g. sensitivity and specificity), and treatment availability were evaluated. The model was applied to the AI-Mind tool, which is currently under development for predicting MCI to dementia risk. In a clinical situation, with no widely applicable and highly effective disease-modifying treatment available, implementing a dementia risk prediction tool leads to lower QALYs and higher costs compared to current practice without such a prediction tool (9.32 vs 9.36 QALYs and €115,837 vs €115,032 for the analyses in this paper). This loss in QALYs was caused by the impact on quality of life associated with predicted dementia conversion risk. Risk prediction followed by efficient treatment strategies based on the predicted risk could lead to a cost-effective alternative in case of specific treatment characteristics. These findings suggest that standalone (i.e. without highly effective treatment options) use of a dementia risk prediction tool may not be cost-effective, but it could result in a cost-effective alternative in combination with a treatment with favourable efficacy and cost profile. Graphical abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Effects of electromagnetic fields from an alternating current power cable on the embryogenesis of three benthic associated marine species - Silvia Paoletti; Robin Brabant; Ilona Strammer; Peter Sigray; Niklas Rolleberg; Brian G. Stewart; Johan Aerts; Steven Degraer; Zoë L. Hutchison; Andrew B. Gill (Marine Environmental Research, 2026)

Cross-linking milk proteins with glyceraldehyde - Robin J. Hunter; Skelte G. Anema (International Dairy Journal, 2026)

A Comparison of Diving Behavior of Goose‐Beaked and Dense‐Beaked Whales From Tagging Studies in Multiple Ocean Basins - Jay Barlow; Robin W. Baird; Janelle Badger; Gregory S. Schorr; Erin A. Falcone; Shannon N. Coates; Peter L. Tyack; Andrew J. Read; Leigh S. Hickmott; John W. Durban; Diane Claridge; Natacha Aguilar de Soto; et al. (Marine Mammal Science, 2026)
Studies of cetacean diving behavior in multiple locations in different ocean basins allow for an assessment of variability within and among populations. We examine foraging dive behaviors of goose‐beaked whales ( Ziphius cavirostris ) and dense‐beaked whales ( Mesoplodon densirostris ) using data from 132 tagged whales in seven locations in the Pacific and Atlantic Oceans and the Mediterranean Sea. Acoustic recording tags are used to identify foraging dives by the presence of echolocation. For other tag types, foraging dives are identified based on maximum dive depth. Five parameters are used to characterize foraging dives: maximum dive depth, foraging dive duration, dive cycle duration, and the mean and standard deviation of echolocation depths. We find that differences among dives within one tagged individual are typically larger than the differences among individuals or among locations, and that differences among individuals are typically similar in magnitude to differences among locations. Regression is used to estimate the mean and standard deviation of echolocation depths from maximum dive depth for dives without acoustic data. Composite values of foraging dive parameters (and standard deviations) are estimated as the average of all study locations.

Nutrient variability drivers in shallow coastal waters of the Eastern Arabian Sea during winter monsoon with implications for coastal productivity - Harikrishna Prasad Mamidala; D. Ganguly; R. Purvaja; R.S. Robin; G. Hariharan; Subbareddy Bonthu; R. Ramesh (Journal of Marine Systems, 2025)

Lithologies of Dimorphos revealed by boulder morphological classes - F. Tusberti; M. Pajola; L. Penasa; A. Lucchetti; M. Massironi; G. Munaretto; J. Beccarelli; R. Pozzobon; C. Rossi; G. Poggiali; N. Murdoch; C.Q. Robin; et al. (Icarus, 2025)

Integrative use of conventional and DNA metabarcoding methods reveals high diversity, prevalence and intensity of gastrointestinal parasites in pigs from Victoria, Australia - Ghazanfar Abbas; Yuet On Lee; Hannah Mitchell; Abdul Ghafar; Mark A. Stevenson; Charles G. Gauci; Leah G. Starick; Regina M. Fogarty; Bernie Gleeson; Dianne E. Phillips; Tao Wang; Robin B. Gasser; et al. (Research in Veterinary Science, 2025)

Bayesian latent class analyses show that serological testing outperforms conventional diagnostic methods for the detection of Ascaris in (individual) pigs - Ghazanfar Abbas; Hannah Mitchell; Mark Stevenson; Yuet On Lee; Abdul Ghafar; Charles Gauci; Hagan Brodziak; Leah G. Starick; Regina M. Fogarty; Bernie Gleeson; Dianne Phillips; Tao Wang; et al. (The Veterinary Journal, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

On court wingwave® coaching improves accuracy and confidence in basketball athletes - Frank P. G. Weiland; Robin Schrödter; Karsten E. Schul; Stefanie Klatt (German Journal of Exercise and Sport Research, 2025)
The short-term oriented coaching method known as wingwave® (Besser-Siegmund Institute, Hamburg, Germany) has demonstrated efficacy in boosting individuals’ confidence related to future tasks, enhancing overall performance in sports motor tasks, and improving concentration abilities. Its procedure incorporates elements of eye movement and desensitization and reprocessing (EMDR) and adds a muscular strength test to reduce stress and anxiety for the athletes. In this study, amateurs and experts were observed performing a basketball-specific task. In two sets of 30 free throws, with a 1 h break between sets, 44 participants (aged 16–32), consisting of 22 experts and 22 novices in basketball, were randomly assigned to either the experimental or control group. The experimental group received one coaching session using the wingwave® method during the break. During coaching, specific emotional obstacles or blockades were identified and addressed using the wingwave® method by six qualified coaches. The findings reveal a statistically significant increase in accuracy, F (1.40) = 4.74, p = 0.036, η 2 = 0.106, Wilk’s Λ = 0.894, in free throws as well as a notable boost in task-specific confidence (i.e., subjective perception; F (1.40) = 4.21, p = 0.047, η 2 = 0.095, Wilk’s Λ = 0.905) in the experimental group compared to the control group. Based on these findings, it can be deduced that the wingwave® method holds promise as a valuable tool for mitigating stress and anxiety, while bolstering self-assurance and fostering confidence in one’s own capabilities within a defined sporting context.

Marker Assisted Introgression and Evaluation of Retinol Equivalent Carotenoid in the Elite Cultivars Background from Traditional Landrace ‘Kavuni’ - Suvarna Rani Chimmili; G. Subashini; M. Raveendran; C. R. Anandakumar; Jyothi Badri; Divya Balakrishnan; S. Robin (Agricultural Research, 2025)

Impacts of orthophosphate addition on chloramine decay and biofilm development in a model drinking water distribution system - Mahmoud H. Badawy; Mitchell G. Cooke; Kimia Aghasadeghi; Sigrid Peldszus; Robin M. Slawson; Peter M. Huck (Water Research, 2025)

Impact of hydrolysable and condensed tannin sources and levels on in vitro equine cecal fermentation - Lauren R. Wottlin; Robin C. Anderson; Raghavendra Bhatta; Jessica Leatherwood; Elena G. Olson; Todd R. Callaway; Steven C. Ricke (Research in Veterinary Science, 2025)

Toxicological concerns regarding glyphosate, its formulations, and co-formulants as environmental pollutants: a review of published studies from 2010 to 2025 - Szandra Klátyik; Gergely Simon; Eszter Takács; Marianna Oláh; Johann G. Zaller; Michael N. Antoniou; Charles Benbrook; Robin Mesnage; András Székács (Archives of Toxicology, 2025)
Over the last decade and worldwide, an enormous investment in research and data collection has been made in the hope of better understanding the possible ecological and toxicological impacts triggered by glyphosate (GLY). This broad-spectrum, systemic herbicide became the most heavily applied pesticide ever in the 2000s. It is sprayed in many different ways in both agricultural and non-agricultural settings, resulting in multiple routes of exposure to organisms up and down the tree of life. Yet, relatively little is known about the environmental fate of GLY-based herbicide (GBH) formulations, and even less on how GBH co-formulants alter the absorption, distribution, metabolism, excretion, and toxicity of GLY. The environmental fate of GLY depends on several abiotic and biotic factors. As a result of heavy annual GBH use over several decades, GLY residues are ubiquitous, and sometimes adversely affect non-target terrestrial and aquatic organisms. GLY has become a frequent contaminant in drinking water and food chains. Human exposures have been associated with numerous adverse health outcomes including carcinogenicity, metabolic syndrome, and reproductive and endocrine-system effects. Nonetheless, the existence and magnitude of GLY-induced effects on human health remain in dispute, especially in the case of heavily exposed applicators. A wide range of biochemical/physiological modes of action have been elucidated. Various GBH co-formulants have long been considered as inert ingredients relative to herbicidal activity but clearly contribute to GLY-induced hazards and risk gradients. In light of already-identified toxicological and ecosystem impacts, the intensive research focuses on GLY and GBHs should continue, coupled in the interim with commonsense, low-cost changes in use patterns and label requirements crafted to slow the spread of GLY-resistant weeds and reduce applicator and general-population exposures.

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

Performance of Molecular Culture ID in diagnosis of bacterial pericarditis - Martine P. Bos; Maria Miguélez Sánchez; Lauren Remijas; Robin van Houdt; Edgar J. G. Peters; Andries E. Budding (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Associations of anthropogenic activity and tributaries with the physicochemical, nutrient and microbial composition of the Ganga (Ganges) River, India - Gillian E. Clayton; Laura A. Richards; Bethany G. Fox; Robin M.S. Thorn; Michael J. Bowes; Daniel S. Read; Holly J. Tipper; Kieran Khamis; Tapan K. Dutta; Arun Kumar; Moushumi Hazra; Ben Howard; et al. (Water Research, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Preoperative physical resilience indicators and their associations with postoperative outcomes - Marjolein Klop; René J. F. Melis; G. M. E. E. Geeske Peeters; Guillaume S. C. Geuzebroek; Robin H. Heijmen; Richard J. A. van Wezel; Jurgen A. H. R. Claassen (GeroScience, 2025)
The health benefit of surgery in older adults may be outweighed by negative effects on cognitive or physical function. Physical resilience is defined as the potential for recovery after a stressor such as surgery. We assessed associations between physical resilience measured by orthostatic blood pressure (BP) and cerebral oxygenation recovery or grip work (sustained hand grip strength; GW) and postoperative outcome in two cohorts of (older) surgical patients. The first cohort (CTC) consisted of patients undergoing complex cardiothoracic surgery. The second cohort (GRR) held geriatric outpatients undergoing various surgical procedures. Outcome measures were length of stay (LoS) and postoperative complications. Negative binomial (LoS) and ordinal (complications) regression models were used to determine associations. 261 patients (113 CTC and 148 GRR) underwent surgery. Median LoS was 10 (CTC) and 5 days (GRR). Postoperative complications occurred in 80% (CTC) and 45% (GRR) of patients. In CTC, 10 mmHg higher systolic BP recovery was associated with a 12% shorter LoS (incidence rate ratio (IRR) 0.88 (95% CI 0.78–0.98)). 10 s longer sustained hand grip was associated with a 5% shorter LoS in GRR (IRR 0.95 (0.90–1.00)), but a 7% longer LoS in CTC (IRR 1.07 (1.03–1.11)). No significant associations were found with postoperative complications. Orthostatic cerebral oxygenation recovery in CTC was not significantly associated with any postoperative outcome. Our results imply that resilience indicators might be associated with LoS after surgery. Future research should seek to replicate our findings and investigate whether adding resilience parameters to preoperative assessment can support postoperative outcome prediction.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

A Metapopulation Model to Assess Water Management Impacts on the Threatened Australian Lungfish, Neoceratodus forsteri - Charles R. Todd; Andrew J. McDougall; Scott M. C. Raymond; Robin Hale; Timothy R. Brown; John D. Koehn; Henry F. Wootton; Steven G. Brooks; Adrian M. Kitchingman; Tom Espinoza; Benjamin G. Fanson; Peter K. Kind; et al. (Fishes, 2025)
The Australian lungfish, Neoceratodus forsteri, is one of the world’s oldest vertebrate lineages, with a slow life-history and threatened status, requiring immediate conservation efforts. The main threats to lungfish populations are degradation and availability of key macrophyte habitats, water regulation and flow modification. As this long-lived species (at least 77 years) has delayed maturity (mature at 10 years), field monitoring alone will not be enough to inform the challenge of ensuring sustainable populations. A stochastic metapopulation model was developed for the Burnett River (Southeast Queensland, Australia), an important habitat for the lungfish that is a highly regulated system with extensive water infrastructure. The model consists of three interacting populations, where the ecology and biology of the species were translated into an 80-year-class population projection matrix for each population, each with post-development streamflow, habitat and movement rules. The model highlights the longer-term interaction between dams and stream flows on habitat availability and subsequent recruitment. Through a pre-development streamflow, we quantify the impact of high regulation and development on the lungfish population in the Burnett River: a minor decline in the upstream population (e.g., 9.8% decline), a large decline in the middle population (64.2% decline), virtually no change in the downstream population (e.g., 1.2% decline) and a moderate decline in the overall metapopulation (e.g., 22.3% decline). The loss of spawning and feeding habitat remains the main reason for population decline, with implications that the loss will lead to greater pressure on remaining downstream habitat due to combined flow and dam effects and, in turn, to extended periods of recovery of spawning habitat. Our modeling approach substantially advances conservation management of this species, as it can be adapted to suit other populations in other river systems and used to test sensitivity to recovery actions.

Distance From Nest and Climate Explain Geographical Trends of Harvester Ant's Food Resource Use: A Multi‐Species Approach - Diego Anjos; Pedro Luna; Kleber Del‐Claro; Rodrigo G. Pol; Javier Lopez de Casenave; Helena Maura Torezan‐Silingardi; Martha L. Baena; Florencia Baudino; Judie Bronstein; Melissa Burt; Eduardo Calixto; Ana Laura Cao; et al. (Journal of Biogeography, 2025)
Main Animals not only forage for abundant and nearby resources, but their diets can also be influenced by abiotic and geographic factors. This often results in non‐random interactions among species. We investigate how seed density, distance from nest, abiotic (e.g., climate stability, temperature, precipitation) and geographic factors (e.g., latitude, elevation and continental hemisphere) influence the removal of food items (i.e., seeds and dead arthropods) by Pogonomyrmex species. Location South and North America, from Patagonia to the Rocky Mountains. Taxon Genus Pogonomyrmex (Formicidae: Hymenoptera). Methods Conducting standardised experiments, we performed a seed removal experiment and an assessment of the items retrieved by ant workers of 160 nests from eight Pogonomyrmex spp. at 16 sites extending the American continent. Results Pogonomyrmex ants native to North America removed more seeds than their South American counterpart. In general, results align with optimal foraging theory, indicating a higher probability of seed removal near ant nests. High climate stability correlated with lower seed predation rates, emphasising seed consumption's significance in historically arid environments. Increased precipitation and temperature led to reduced removal of food resources, suggesting reduced water availability and lower mean temperatures increases the consumption of seeds by harvester ants. Conclusions Overall, Pogonomyrmex ants' food resource use is influenced by a combination of factors such as region, distance from the nest and climate. This study underscores harvester ants' potential impact on plant distribution over large spatial scales consuming seeds from the immediate proximity of their nest and preventing establishment.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Morphometric characteristics and spatiotemporal heterogeneity of microplastics on the north-east coast of India - I. Anandavelu; R. Karthik; R.S. Robin; G. Hariharan; M. Mugilarasan; R. Ramesh; R. Purvaja (Journal of Hazardous Materials, 2024)

Microplastics in the Eastern Arabian Sea: Decision support tools for monitoring and environmental risk reduction - M. Mugilarasan; R.S. Robin; J. Joyson Joe Jeevamani; R. Karthik; A. Nithin; G. Hariharan; B. Subbareddy; K.K. Idrees Babu; R. Purvaja (Journal of Environmental Management, 2024)

Luteodiscus gen. nov. (Hyphodiscaceae, Helotiales), with L. epibryus comb. nov. and L. hemiamyloideus sp. nov., two overlooked bryophilous ascomycetes with a wide host range - Hans-Otto Baral; Lothar G. Krieglsteiner; Zuzana Sochorová; Peter Döbbeler; Jean-Paul Priou; Elisabeth Stöckli; Enrique Rubio; François Valade; Günter Bauer; Michel Hairaud; Robin Isaksson; George Greiff; et al. (Mycological Progress, 2024)

Seismicity in Central America (1520–2020) and Earthquake catalog compilation for seismic hazard assessments - Carlos Gamboa-Canté; Mario Arroyo-Solórzano; Belén Benito; Jorge Aguilar; Ivonne G. Arroyo; Eduardo Camacho-Astigarrabia; Diego Castro; Omar Flores; Lepolt Linkimer; Martha Griselda Marroquin; Luis Mixco-Durán; Wilfried Strauch; et al. (Bulletin of Earthquake Engineering, 2024)

Geology from aeromagnetic data - Peter G. Betts; David Moore; Alan Aitken; Teagan Blaikie; Mark Jessell; Laurent Ailleres; Robin Armit; Mark McLean; Radhakrishna Munukutla; Chibuzo Chukwu (Earth-Science Reviews, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Genome of a single worker of the greenhead ant, Rhytidoponera metallica, reveals mechanisms of toxin evolution in a genetically hyperdiverse eusocial species - Anders Isaksen; Pedro G. Nachtigall; Robin A. Araya; Marius F. Maurstad; Samuel D. Robinson; Thomas F. Hansen; Eivind A.B. Undheim (Toxicon, 2024)

Correction: Progress in the analysis of English Channel loliginid squid diets using DNA-metabarcoding techniques - A. Larivain; C. Zatylny-Gaudin; E. Gonzalez; G. J. Pierce; A. M. Power; J. P. Robin (Marine Biology, 2024)

Characterizing genetic diversity of Sclerotium rolfsii isolates by biomapping of mycelial compatibility groupings and multilocus sequence analysis - C. Shanmugaraj; Deeba Kamil; Robin Gogoi; Amrita Das; G. M. Sandeep Kumar; Zakir Hussain; Praveen Kumar Singh; M. A. Iquebal (World Journal of Microbiology and Biotechnology, 2024)

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Retrospective Risk Assessment of Injuries and Fatalities in the Forestry and Logging Workforce in the United States, 2003-2019 - Heidi Knecht; Jo Anne G Balanay; Ricky Langley; Robin Tutor Marcom; Stephanie L. Richards (Journal of Agromedicine, 2024)

The temporal-spatial evolution of handaxe technology in China: Recent progress and future directions - Hao Li; Shejiang Wang; Matt G. Lotter; Robin Dennell; Kathleen Kuman; Fahu Chen (Science Bulletin, 2024)

Progress in the analysis of English Channel loliginid squid diets using DNA-metabarcoding techniques - A. Larivain; C. Zatylny-Gaudin; E. Gonzalez; G. J. Pierce; A. M. Power; J. P. Robin (Marine Biology, 2024)

A call to rename Ziphius cavirostris the goose‐beaked whale: promoting inclusivity and diversity in marine mammalogy by re‐examining common names - Ashley D. Rogers; Aileen Lavelle; Robin W. Baird; Arona Bender; Anna Borroni; Gustavo Cárdenas Hinojasa; William R. Cioffi; Brianna W. Elliott; Craig Harms; Anne E. Harshbarger; Ann‐Marie Jacoby; Kathryn Lienhard; et al. (Marine Mammal Science, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Scratch circles and circular purported ammoglyphs: Novel observations from the Cape south coast of South Africa - Charles W. Helm; Robin M. Catchpole; Hayley C. Cawthra; Richard M. Cowling; Jan C. De Vynck; Mark G. Dixon; Renée Rust; Willo Stear; Guy H.H. Thesen (Proceedings of the Geologists' Association, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Fungal endophytes of the invasive grass Eragrostis lehmanniana shift metabolic expression in response to native and invasive grasses - Taylor A. Portman; A. Elizabeth Arnold; Robin G. Bradley; Jeffrey S. Fehmi; Craig Rasmussen; Malak M. Tfaily (Fungal Ecology, 2024)

Effect of Flow Variability on Dispersion of Continuous and Puff Releases in a Regular Street Network - T. Auerswald; K. Klippel; T. G. Thomas; E. V. Goulart; M. Carpentieri; P. Hayden; D. Hertwig; N. C. Reis; A. Robins; O. Coceal (Boundary-Layer Meteorology, 2024)

Systematic Review of Biological, Chemical, Ergonomic, Physical, and Psychosocial Hazards Impacting Occupational Health of United States Forestry Workers - Heidi Knecht; Jo Anne G Balanay; Ricky Langley; Robin Tutor Marcom; Stephanie L Richards (Journal of Forestry, 2024)
Forestry is one of the most hazardous occupations, due in part to the biological, chemical, ergonomic, physical, and psychosocial aspects of the job. Here, we review health risks in forestry occupations, including those in professional and technical forestry, logging, and forestry support, from the standpoint of biological (e.g., insects/arachnids, plants), chemical (e.g., diesel exhaust), ergonomic (e.g., awkward postures, forceful motions), physical (temperature, noise, vibrations, radiation), and psychosocial (e.g., workplace factors that cause stress, strain, or interpersonal problems for the worker) issues. We conducted a systematic review over a 10-year period (2011–2021) to assess health hazards identified in studies conducted on these occupations and reveal knowledge gaps for future studies to address. This study focuses on occupational health rather than occupational safety. Other forestry worker occupational health and safety studies have focused on analyzing injuries and deaths directly relating to transportation and/or contact with objects such as trees or logs and equipment; however, the areas of occupational health highlighted here have been understudied. Future work should focus on these areas, with an emphasis on intervention strategies that eliminate or mitigate the deleterious health effects of occupational exposures. Study Implications: Forestry workers are exposed to occupational health hazards in their outdoor workplace. This review analyzes published work for a 10-year period (2011–2021) with broader implications such as (1) greater understanding of gaps in the literature for key occupational health hazards facing United States forestry workers and (2) better information on the need for more in-depth studies to collect information about exposure assessments to improve worker protection. This literature review can help forestry workers, managers, and scientists mitigate exposures and protect health.

Assessing impacts of a notorious invader (common carp Cyprinus carpio) on Australia's aquatic ecosystems: Coupling abundance-impact relationships with a spatial biomass model - Benjamin G. Fanson; Robin Hale; Jason D. Thiem; Jarod P. Lyon; John D. Koehn; Andrew F. Bennett; Ivor Stuart (Biological Conservation, 2024)

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Early detection of emerging persistent perfluorinated alkyl substances (PFAS) along the east coast of India - Hariharan G; Sunantha G; Robin R.S.; Darwin R; Purvaja R; Ramesh R (Science of The Total Environment, 2023)

Early and long-distance uptake by Eucalyptus grandis of N, K and Ca tracers injected down to a depth of 7 m - J.P. Bouillet; B Bordron; J.P. Laclau; A. Robin; J.L.M. Gonçalves; C.H. Abreu-Junior; P.C.O Trivelin; Y. Nouvellon; G. le Maire (Forest Ecology and Management, 2023)

MicroRNAs in atrial fibrillation target genes in structural remodelling - Nicoline W. E. van den Berg; Makiri Kawasaki; Fransisca A. Nariswari; Benedetta Fabrizi; Jolien Neefs; Ingeborg van der Made; Robin Wesselink; Wim Jan P. van Boven; Antoine H. G. Driessen; Aldo Jongejan; Joris R. de Groot (Cell and Tissue Research, 2023)
We aim to elucidate how miRNAs regulate the mRNA signature of atrial fibrillation (AF), to gain mechanistic insight and identify candidate targets for future therapies. We present combined miRNA–mRNA sequencing using atrial tissues of patient without AF ( n = 22), with paroxysmal AF ( n = 22) and with persistent AF ( n = 20). mRNA sequencing previously uncovered upregulated epithelial to mesenchymal transition, endothelial cell proliferation and extracellular matrix remodelling involving glycoproteins and proteoglycans in AF. MiRNA co-sequencing discovered miRNAs regulating the mRNA expression changes. Key downregulated miRNAs included miR-135b-5p, miR-138-5p, miR-200a-3p, miR-200b-3p and miR-31-5p and key upregulated miRNAs were miR-144-3p, miR-15b-3p, miR-182-5p miR-18b-5p, miR-4306 and miR-206. MiRNA expression levels were negatively correlated with the expression levels of a multitude of predicted target genes. Downregulated miRNAs associated with increased gene expression are involved in upregulated epithelial and endothelial cell migration and glycosaminoglycan biosynthesis. In vitro inhibition of miR-135b-5p and miR-138-5p validated an effect of miRNAs on multiple predicted targets. Altogether, the discovered miRNAs may be explored in further functional studies as potential targets for anti-fibrotic therapies in AF.

Diversity and distribution of elasmobranchs in the coastal waters of Cyprus: using bycatch data to inform management and conservation - Martha O’Keefe; Elizabeth G. T. Bengil; Josie L. Palmer; Damla Beton; Çiğdem Çağlar; Brendan J. Godley; Meryem Özkan; Robin T. E. Snape; Annette C. Broderick (Frontiers in Marine Science, 2023)
Introduction Loss of biodiversity in marine ecosystems is a globally acknowledged problem. To address this and avoid extinctions, improved conservation is required to protect and restore our oceans. Elasmobranch species are considered the second most threatened vertebrate lineage, with overfishing considered the most important driver of declines. The Mediterranean Sea is a hotspot for elasmobranchs, with the eastern basin considered a data-poor area. Methods This study sought to address that deficiency, using bycatch data to assess the diversity and distribution of elasmobranch species caught as a result of commercial fishing in Northern Cyprus from 2018 to 2022. Results Thirty-six elasmobranch species were recorded, including 24 new records for Northern Cyprus, representing 41% of all species recorded in the Mediterranean. Of these 36 species, 61% are listed on the IUCN Red List as globally threatened (Critically Endangered, Endangered or Vulnerable). Of the species recorded, 71% of sharks (n=17), and 53% of batoids (skates and rays; n=19) are listed as threatened. We present data on the distribution of captures and size classes and infer life stage from these data. Discussion Our study demonstrates the importance of the coastal waters of Cyprus for multiple life stages of a broad range of elasmobranch species. As most elasmobranchs caught are retained for bait, subsistence or trade, our study has highlighted the need to update the regulations for this small-scale fishery, and led to a recent amendment to prohibit trade in all species listed under the Barcelona Convention.

Statistical considerations of using the 1-ft2 quadrat for monitoring peak standing crop and residual dry matter on California annual rangelands - Royce Larsen; Joseph G. Robins; Kevin B. Jensen; Matthew Shapero; Karl Striby; LynneDee Althouse; Melvin George; Marc Horney; Devii Rao; Alexander Hernandez; Randy Dahlgren; James Bartolome (Rangelands, 2023)

Toward decentralized wastewater treatment: A flow-through module using microtubular gas diffusion electrodes for micropollutants removal - Mojtaba Mohseni; Daniel Felder; Korcan Percin; Maximilian Thönes; Matthias Gassenmeier; Robin Kupec; Claudia Weidlich; John Linkhorst; Robert G. Keller; Matthias Wessling (Journal of Hazardous Materials, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Beclin 1 regulates astrocyte phagocytosis and phagosomal recruitment of retromer - Evelyn G. Lemus Silva; Yuberki Delgadillo; Robin E. White; Kurt M. Lucin (Tissue and Cell, 2023)

Solar wind driven influences on the Martian oxygen corona: Constraints on atmospheric sputtering from a synthesis of MAVEN measurements during solar minimum - Robin Ramstad; David A. Brain; Yaxue Dong; Jasper S. Halekas; James M. McFadden; David L. Mitchell; Jared Espley; Francis G. Eparvier; Bruce M. Jakosky (Icarus, 2023)

A Letter to Your Care Providers: Implementation and Analysis of a Letter-based Advance Care Planning Initiative for Gynecologic Oncology Patients - Catherine N. Zivanov; Anne Coogan; Robin R. Lane; Sara G. Lin; Sarah C. Reed; Marc A. Robinson; Mohana Karlekar; Lauren S. Prescott; Alaina J. Brown (Journal of Cancer Education, 2023)

Effect of hydration time on milk protein concentrate (MPC85) solubility and the renneting properties of skim milk fortified with the MPC85 - Robin J. Hunter; Skelte G. Anema (International Dairy Journal, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

An invertebrate model in examining the effect of acute ferric iron exposure on proprioceptive neurons - Mikaela L. Wagers; Ashley Starks; Maya O. Abul-Khoudoud; Sufia M. Ahmed; Abraham W. Alhamdani; Clair Ashley; Patrick C. Bidros; Constance O. Bledsoe; Kayli E. Bolton; Jerone G. Capili; Jamie N. Henning; Bethany J. Ison; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Plant-soil feedback: the next generation - G. Kenny Png; Jonathan R. De Long; Ellen L. Fry; Robin Heinen; Johannes Heinze; Elly Morriën; Sarah J. Sapsford; François P. Teste (Plant and Soil, 2023)

Anthropogenic marine litter: An approach to environmental quality for India's southeastern Arabian Sea coast - M. Mugilarasan; R. Karthik; R.S. Robin; B. Subbareddy; G. Hariharan; I. Anandavelu; T.P.S. Jinoj; R. Purvaja; R. Ramesh (Science of The Total Environment, 2023)

Plant-soil feedback: incorporating untested influential drivers and reconciling terminology - Jonathan R. De Long; Robin Heinen; Johannes Heinze; Elly Morriën; G. Kenny Png; Sarah J. Sapsford; François P. Teste; Ellen L. Fry (Plant and Soil, 2023)
Background Plants condition the soil in which they grow, thereby altering the performance of subsequent plants growing in this soil. This phenomenon, known as plant-soil feedback (PSF), has garnered increasing interest. Experiments are moving from single species soil pairings in the glasshouse to community-level field trials. Consequently, our knowledge of the role PSF plays in shaping ecosystem functions has advanced. However, knowledge gaps remain. Scope Here, we explore intrinsic and extrinsic abiotic and biotic drivers of PSF such as maternal effects, plant functional traits, self-DNA, plant-plant competition, herbivory, interactions between soil organisms, temperature, drought, flooding, greenhouse gases, (micro)nutrients, plant-litter-soil feedback and priority effects. These drivers have begun to feature in experiments, thereby increasing our mechanistic understanding of PSF. Nonetheless, many of these topics have received insufficient coverage to determine general principles across larger temporal and spatial scales. Further, conflicting terminology has excluded PSF studies from reviews and meta-analyses. We review terms such as soil sickness, Janzen-Connell hypothesis, soil-related invasive species work, soil legacies, allelopathy and soil-related succession that overlap with PSF but are generally not named as such. Conclusion Holistic experimental designs that consider the continual reciprocal feedback between the extrinsic environment, plants and soil, as well as the unification of terminologies are necessary if we are to realise the full potential of PSF for understanding and steering ecosystem processes. Here, we compile outstanding questions related to PSF research that emphasis the aforementioned topics and suggest ways to incorporate them into future research in order to advance plant-soil ecology.

Multiple traces of monkeypox detected in non-sewered wastewater with sparse sampling from a densely populated metropolitan area in Asia - Dhammika Leshan Wannigama; Mohan Amarasiri; Parichart Hongsing; Cameron Hurst; Charin Modchang; Sudarat Chadsuthi; Suparinthon Anupong; Phatthranit Phattharapornjaroen; Ali Hosseini Rad S.M.; Stefan Fernandez; Angkana T. Huang; Naris Kueakulpattana; et al. (Science of The Total Environment, 2023)

Active breeding seabirds prospect alternative breeding colonies - Jelena Kralj; Aurore Ponchon; Daniel Oro; Barbara Amadesi; Juan Arizaga; Nicola Baccetti; Thierry Boulinier; Jacopo G. Cecere; Robin M. Corcoran; Anna-Marie Corman; Leonie Enners; Abram Fleishman; et al. (Oecologia, 2023)

Pathways of methane removal in the sediment and water column of a seasonally anoxic eutrophic marine basin - Olga M. Żygadłowska; Jessica Venetz; Robin Klomp; Wytze K. Lenstra; Niels A. G. M. van Helmond; Thomas Röckmann; Anna J. Wallenius; Paula Dalcin Martins; Annelies J. Veraart; Mike S. M. Jetten; Caroline P. Slomp (Frontiers in Marine Science, 2023)
Methane (CH 4 ) is a key greenhouse gas. Coastal areas account for a major proportion of marine CH 4 emissions. Eutrophication and associated bottom water hypoxia enhance CH 4 production in coastal sediments. Here, we assess the fate of CH 4 produced in sediments at a site in a seasonally anoxic eutrophic coastal marine basin (Scharendijke, Lake Grevelingen, the Netherlands) in spring (March) and late summer (September) in 2020. Removal of CH 4 in the sediment through anaerobic oxidation with sulfate ( S O 4 2 - ) is known to be incomplete in this system, as confirmed here by only slightly higher values of δ 13 C-CH 4 and δD-CH 4 in the porewater in the shallow sulfate-methane-transition zone (~5-15 cm sediment depth) when compared to deeper sediment layers. In March 2020, when the water column was fully oxygenated, CH 4 that escaped from the sediment was at least partially removed in the bottom water through aerobic oxidation. In September 2020, when the water column was anoxic below ~35 m water depth, CH 4 accumulated to high concentrations (up to 73 µmol L -1 ) in the waters below the oxycline. The sharp counter gradient in oxygen and CH 4 concentrations at ~35 m depth and increase in δ 13 C-CH 4 and δD-CH 4 above the oxycline indicate mostly aerobic water column removal of CH 4 . Water column profiles of particulate and dissolved Fe and Mn suggest redox cycling of both metals at the oxycline, pointing towards a potential role of metal oxides in CH 4 removal. Water column profiles of N H 4 + and N O 3 - indicate removal of both solutes near the oxycline. Analyses of 16S rRNA gene sequences retrieved from the water column reveal the presence of aerobic CH 4 oxidizing bacteria ( Methylomonadaceae ) and anaerobic methanotrophic archaea ( Methanoperedenaceae ), with the latter potentially capable of N O 3 - and/or metal-oxide dependent CH 4 oxidation, near the oxycline. Overall, our results indicate sediment and water column removal of CH 4 through a combination of aerobic and anaerobic pathways, which vary seasonally. Some of the CH 4 appears to escape from the surface waters to the atmosphere, however. We conclude that eutrophication may make coastal waters a more important source of CH 4 to the atmosphere than commonly assumed.

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Networking and co-occurrence of virulent and multidrug resistant environmental bacteria in different aquatic systems: A gap in MDR-virulence transfer? - C. Saravanakumar; C.S. Neethu; R. Purvaja; G. Sunantha; R.S. Robin; R. Ramesh (Science of The Total Environment, 2023)

Climate change and human health in the Eastern Mediterranean and Middle East: Literature review, research priorities and policy suggestions - Marco Neira; Kamil Erguler; Hesam Ahmady-Birgani; Nisreen DaifAllah AL-Hmoud; Robin Fears; Charalambos Gogos; Nina Hobbhahn; Maria Koliou; Leondios G. Kostrikis; Jos Lelieveld; Azeem Majeed; Shlomit Paz; et al. (Environmental Research, 2023)

How long do bracken (Pteridium aquilinum (L.) Kuhn) control treatments maintain effectiveness? - Ilgın Akpınar; Josu G. Alday; Emma Cox; H.A. McAllister; Michael G. Le Duc; Robin J. Pakeman; Rob H. Marrs (Ecological Engineering, 2023)

Exploring regional coastal sediment pathways using a coupled tide-wave-sediment dynamics model - A.G. Davies; P.E. Robins; M. Austin; G. Walker-Springett (Continental Shelf Research, 2023)

Historic Spatial Patterns of Storm-Driven Compound Events in UK Estuaries - C. Lyddon; P. Robins; M. Lewis; A. Barkwith; G. Vasilopoulos; I. Haigh; T. Coulthard (Estuaries and Coasts, 2023)
Compound estuarine flooding is driven by extreme sea-levels and river discharge occurring concurrently, or in close succession, and threatens low-lying coastal regions worldwide. We hypothesise that these drivers of flooding rarely occur independently and co-operate at sub-daily timescales. This research aimed to identify regions and individual estuaries within Britain susceptible to storm-driven compound events, using 27 tide gauges linked to 126 river gauges covering a 30-year record. Five methods were evaluated, based on daily mean, daily maximum, and instantaneous 15-min discharge data to identify extremes in the river records, with corresponding skew surges identified within a ‘storm window’ based on average hydrograph duration. The durations, relative timings, and overlap of these extreme events were also calculated. Dependence between extreme skew surge and river discharge in Britain displayed a clear east–west split, with gauges on the west coast showing stronger correlations up to 0.33. Interpreting dependence based on correlation alone can be misleading and should be considered alongside number of historic extreme events. The analyses identified 46 gauges, notably the Rivers Lune and Orchy, where there has been the greatest chance and most occurrences of river-sea extremes coinciding, and where these events readily overlapped one another. Our results were sensitive to the analysis method used. Most notably, daily mean discharge underestimated peaks in the record and did not accurately capture likelihood of compound events in 68% of estuaries. This has implications for future flood risk in Britain, whereby studies should capture sub-daily timescale and concurrent sea-fluvial climatology to support long-term flood management plans.

The serotonin receptor 3E variant is a risk factor for female IBS-D - Nikola Fritz; Sabrina Berens; Yuanjun Dong; Cristina Martínez; Stefanie Schmitteckert; Lesley A. Houghton; Miriam Goebel-Stengel; Verena Wahl; Maria Kabisch; Dorothea Götze; Mauro D’Amato; Tenghao Zheng; et al. (Journal of Molecular Medicine, 2022)
Irritable bowel syndrome (IBS) is a gut-brain disorder of multifactorial origin. Evidence of disturbed serotonergic function in IBS accumulated for the 5-HT 3 receptor family. 5-HT 3 Rs are encoded by HTR3 genes and control GI function, and peristalsis and secretion, in particular. Moreover, 5-HT 3 R antagonists are beneficial in the treatment of diarrhea predominant IBS (IBS-D). We previously reported on functionally relevant SNPs in HTR3A c.-42C > T (rs1062613), HTR3C p.N163K (rs6766410), and HTR3E c.*76G > A (rs56109847 = rs62625044) being associated with IBS-D, and the HTR3B variant p.Y129S (rs1176744) was also described within the context of IBS. We performed a multi-center study to validate previous results and provide further evidence for the relevance of HTR3 genes in IBS pathogenesis. Therefore, genotype data of 2682 IBS patients and 9650 controls from 14 cohorts (Chile, Germany (2), Greece, Ireland, Spain, Sweden (2), the UK (3), and the USA (3)) were taken into account. Subsequent meta-analysis confirmed HTR3E c.*76G > A (rs56109847 = rs62625044) to be associated with female IBS-D (OR = 1.58; 95% CI (1.18, 2.12)). Complementary expression studies of four GI regions (jejunum, ileum, colon, sigmoid colon) of 66 IBS patients and 42 controls revealed only HTR3E to be robustly expressed. On top, HTR3E transcript levels were significantly reduced in the sigma of IBS patients ( p = 0.0187); more specifically, in those diagnosed with IBS-D ( p = 0.0145). In conclusion, meta-analysis confirmed rs56109847 = rs62625044 as a risk factor for female IBS-D. Expression analysis revealed reduced HTR3E levels in the sigmoid colon of IBS-D patients, which underlines the relevance of HTR3E in the pathogenesis of IBS-D.

Comparison of Three Automated Approaches for Classification of Amyloid-PET Images - Ying-Hwey Nai; Yee-Hsin Tay; Tomotaka Tanaka; Christopher P. Chen; Edward G. Robins; Anthonin Reilhac (Neuroinformatics, 2022)

Association between toxic and essential metals in blood and global DNA methylation among electronic waste workers in Agbogbloshie, Ghana - Ibrahim Issah; John Arko-Mensah; Laura S. Rozek; Katie R. Zarins; Duah Dwomoh; Thomas P. Agyekum; Niladri Basu; Stuart Batterman; Thomas G. Robins; Julius N. Fobil (Environmental Science and Pollution Research, 2022)

Worldwide phylogeography of rough‐toothed dolphins ( Steno bredanensis ) provides evidence for subspecies delimitation - G. Renee Albertson; Alana Alexander; Frederick I. Archer; Susana Caballero; Karen K. Martien; Lenaïg G. Hemery; Robin W. Baird; Marc Oremus; M. Michael Poole; Deborah A. Duffield; Robert L. Brownell; Dan Kerem; et al. (Marine Mammal Science, 2022)
Rough‐toothed dolphins ( Steno bredanensis ) have a global tropical and subtropical distribution with oceanic, neritic, and island‐associated populations. To inform conservation and management for this species, we used sequences from the mtDNA control region ( n = 360), mitogenomes ( n = 19), and six nuclear introns ( n = 35) to provide multiple lines of evidence to critically evaluate the potential taxonomic status of rough‐toothed dolphins. Using samples from the Pacific, Indian, and Atlantic Oceans, we examined the null hypothesis that rough‐toothed dolphins are one panmictic species and the alternate hypothesis of oceanic subspecies. Phylogenetic analyses of mitogenomes revealed a private Atlantic clade sister to a larger cosmopolitan clade including individuals from all tropical and subtropical oceans. We dated the split between the Atlantic clade and the cosmopolitan clade to 890,000 years ago. We determined that Atlantic rough‐toothed dolphins could be correctly diagnosed with 98% accuracy with the mtDNA control region and calculated the net nucleotide divergence as 0.02. Population level analyses revealed significant genetic differentiation using mtDNA among most regions, while significant differentiation using nuclear markers occurred only between the Atlantic and the Indian/Pacific regions. Therefore, the oceanic divergence and diagnosability of rough‐toothed dolphins in the Atlantic and the Indian/Pacific Oceans meet proposed criteria for recognition as two subspecies.

New Alien Mediterranean Biodiversity Records (August 2022) - FRANCESCO TIRALONGO; OKAN AKYOL; SARA A.A. AL MABRUK; PIETRO BATTAGLIA; DAMLA BETON; BANU BITLIS; JOSEPH A. BORG; MARC BOUCHOUCHA; MELIH ERTAN ÇINAR; FABIO CROCETTA; BRANKO DRAGIČEVIĆ; Jakov DULČIĆ JDULČIĆ; et al. (Mediterranean Marine Science, 2022)
In this Collective Article on alien and cryptogenic diversity in the Mediterranean Sea we report a total of 19 species belonging to nine Phyla and coming from nine countries. Several of these records concern fish species, and of particular interest are the first records of: Terapon puta for Italian waters; Pteragopus trispilus from Malta; Plotosus lineatus from Cyprus; and the northernmost Mediterranean record of Lagocephalus sceleratus. The northernmost Mediterranean record was also reported for the sea urchin Diadema setosum. The portunid crab Thalamita poissonii was recorded for the first time in Libya. The copepod Pseudodiaptomus marinus was recorded for the first time in the Marmara Sea. The polychaete Branchiomma luctuosum was recorded for the first time from the Mediterranean coast of France. The alien anemone Diadumene lineata was recorded for the first time from Slovenia. The macroalgae Sargassum furcatum was recorded for the first time from Italy. The new Mediterranean records here reported help tracing abundance and distribution of alien and cryptic species in the Mediterranean Sea.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Correction to: Associations Between Two Measures of Trunk Muscular Endurance Among Male Law Enforcement Officers - J. Jay Dawes; Cody A. Stahl; Robert G. Lockie; Jan E. Redmond; Charlie Kornhauser; Ryan J. Holmes; Robin M. Orr (Journal of Science in Sport and Exercise, 2022)

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The natural history of OTOF-related auditory neuropathy spectrum disorders: a multicenter study - Ryan K. Thorpe; Hela Azaiez; Peina Wu; Qiuju Wang; Lei Xu; Pu Dai; Tao Yang; G. Bradley Schaefer; B. Robert Peters; Kenny H. Chan; Krista S. Schatz; Joann Bodurtha; et al. (Human Genetics, 2022)

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

Compensatory responses to increased mechanical abnormalities in COPD during sleep - Nicolle J. Domnik; Devin B. Phillips; Matthew D. James; Grace A. Ayoo; Sarah M. Taylor; Robin E. Scheeren; Amanda T. Di Luch; Kathryn M. Milne; Sandra G. Vincent; Amany F. Elbehairy; Sophie J. Crinion; Helen S. Driver; et al. (European Journal of Applied Physiology, 2022)

Systematic assessment of acquisition and data-processing parameters in the suspect screening of veterinary drugs in archive matrices using LC-HRMS - Larissa J. M. Jansen; Rosalie Nijssen; Yvette J. C. Bolck; Robin S. Wegh; Milou G. M. van de Schans; Bjorn J. A. Berendsen (Food Additives & Contaminants: Part A, 2022)

Establishment of a microsatellite genetic baseline for North American Atlantic sturgeon (Acipenser o. oxyrhinchus) and range-wide analysis of population genetics - Shannon L. White; David C. Kazyak; Tanya L. Darden; Daniel J. Farrae; Barbara A. Lubinski; Robin L. Johnson; Michael S. Eackles; Matthew T. Balazik; Harold M. Brundage; Adam G. Fox; Dewayne A. Fox; Christian H. Hager; et al. (Conservation Genetics, 2021)

Associations Between Two Measures of Trunk Muscular Endurance Among Male Law Enforcement Officers - J. Jay Dawes; Cody A. Stahl; Robert G. Lockie; Jan E. Redmond; Charles L. Kornhauser; Ryan J. Holmes; Robin M. Orr (Journal of Science in Sport and Exercise, 2021)

Global DNA (LINE-1) methylation is associated with lead exposure and certain job tasks performed by electronic waste workers - Ibrahim Issah; John Arko-Mensah; Laura S. Rozek; Katie R. Zarins; Thomas P. Agyekum; Duah Dwomoh; Niladri Basu; Stuart Batterman; Thomas G. Robins; Julius N. Fobil (International Archives of Occupational and Environmental Health, 2021)

Biofunctional significance of multi-herbal combination against paracetamol-induced hepatotoxicity in Wistar rats - Pardeep Kaur; Robin Shergill; Rajendra G. Mehta; Balbir Singh; Saroj Arora (Environmental Science and Pollution Research, 2021)

Global high-throughput genotyping of organellar genomes reveals insights into the origin and spread of invasive starry stonewort (Nitellopsis obtusa) - Robin S. Sleith; Kenneth G. Karol (Biological Invasions, 2021)
Aquatic invasive species are damaging to native ecosystems. Preventing their spread and achieving comprehensive control measures requires an understanding of the genetic structure of an invasive population. Organellar genomes (plastid and mitochondrial) are useful for population level analyses of invasive plant distributions. In this study we generate complete organellar reference genomes using PacBio sequencing, then use these reference sequences for SNP calling of high-throughput, multiplexed, Illumina based organellar sequencing of fresh and historical samples from across the native and invasive range of Nitellopsis obtusa (Desv. in Loisel.) J.Groves, an invasive macroalgae. The data generated by the analytical pipeline we develop indicate introduction to North America from Western Europe. A single nucleotide transversion in the plastid genome separates a group of five samples from Michigan and Wisconsin that either resulted from introductions of two closely related genotypes or a mutation that has arisen in the invasive range. This transversion will serve as a useful tool to understand how Nitellopsis obtusa moves across the landscape. The methods and analyses described here are broadly applicable to invasive and native plant and algae species, and allow efficient genotyping of variable quality samples, including 100-year-old herbarium specimens, to determine population structure and geographic distributions.

Status of health and conservation classification of tropical coral reefs in Lakshadweep archipelago - M. Gopi; J. Joyson Joe Jeevamani; S. Goutham; Nina Tabitha Simon; V. Deepak Samuel; K. R. Abhilash; R. S. Robin; G. Hariharan; R. Muruganandam; P. Krishnan; R. Purvaja; R. Ramesh (Wetlands Ecology and Management, 2021)

Female song in the Cyprus Wheatear Oenanthe cypriaca - Robert Patchett; Alexander N. G. Kirschel; Joanna Robins King; Patrick Styles; Will Cresswell (Journal of Ornithology, 2021)
Female song is widespread across bird species yet rarely reported. Here, we report the first observations and description of female song in the Cyprus Wheatear Oenanthe cypriaca and compare it to male song through the breeding season. Twenty-five percent of colour-ringed females were observed singing at least once, predominantly in April, compared to 71% of males that continued singing through the breeding period. We suggest that female song may have multiple functions in this species, but it may be especially important in territorial defence and mate acquisition.

The impact of COVID-19 on acute stroke care in Belgium - Vincent Raymaekers; Jelle Demeestere; Flavio Bellante; Sofie De Blauwe; Sylvie De Raedt; Anne Dusart; Lise Jodaitis; Robin Lemmens; Caroline Loos; Ligot Noémie; Matthieu P. Rutgers; Fenne Vandervorst; et al. (Acta Neurologica Belgica, 2021)

Induction of metallothionein in the common bully ( Gobiomorphus cotidianus ) from the Motueka River - Louis A. Tremblay; Katherine Trought; Thomas J. Sheehan; Robin J. P. Holmes; Andrew Barrick; Roger G. Young (New Zealand Journal of Marine and Freshwater Research, 2021)
The Motueka catchment is a major river system in the South Island, New Zealand, typically considered to be of ‘good water quality’. The catchment has high metal inputs originating from a mineral belt in the headwaters. This study investigated the induction of metallothionein (MT) in the common bully, Gobiomorphus cotidianus , to assess exposure to trace metal contamination in the Motueka River. The results showed a significant increase in MT induction in both the gill and liver tissue samples from fish collected in the Motueka River compared to a reference site in the Brooklyn Stream tributary. This effect is likely modulated by the higher nickel levels originating from the Red Hills that accumulated in the sediment of the Motueka River.

Assessment of future climate change impact on rainfed wheat yield in the semi-arid Eastern High Plain of Algeria using a crop model - Tassadit Kourat; Dalila Smadhi; Brahim Mouhouche; Nerdjes Gourari; M. G. Mostofa Amin; Christopher Robin Bryant (Natural Hazards, 2021)

Climate and socio‐economic factors explain differences between observed and expected naturalization patterns of European plants around the world - Robin Pouteau; Wilfried Thuiller; Carsten Hobohm; Caroline Brunel; Barry J. Conn; Wayne Dawson; Michele de Sá Dechoum; Aleksandr L. Ebel; Franz Essl; Ori Fragman‐Sapir; Trevor Fristoe; Nejc Jogan; et al. (Global Ecology and Biogeography, 2021)
Aim The number of naturalized (i.e. established) alien species has increased rapidly over recent centuries. Given the differences in environmental tolerances among species, little is known about what factors determine the extent to which the observed size of the naturalized range of a species and hence the extent to which the observed richness of naturalized species of a region approach their full potential. Here, we asked which region‐ and species‐specific characteristics explain differences between observed and expected naturalizations. Location Global. Time period Present. Major taxa studied Vascular plants. Methods We determined the observed naturalized distribution outside Europe for 1,485 species endemic to Europe using the Global Naturalized Alien Flora (GloNAF) database and their expected distributions outside Europe using species distribution models. First, we investigated which of seven socio‐economic factors related to introduction pathways, anthropogenic pressures and inventory effort best explained the differences between observed and expected naturalized European floras. Second, we examined whether distributional features, economic use and functional traits explain the extent to which species have filled their expected ranges outside Europe. Results In terms of suitable area, more than 95% of expected naturalizations of European plants were not yet observed. Species were naturalized in only 4.2% of their suitable regions outside of Europe (range filling) and in 0.4% of their unsuitable regions (range expansion). Anthropogenic habitat disturbance primarily explained the difference between observed and expected naturalized European floras, as did the number of treaties relevant to invasive species. Species of ornamental and economic value and with large specific leaf area performed better at filling and expanding beyond their expected range. Main conclusions The naturalization of alien plant species is explained by climate matching but also by the regional level of human development, the introduction pressure associated with the ornamental and economic values of the species and their adaptation to disturbed environments.

Population structure in a continuously distributed coastal marine species, the harbor porpoise, based on microhaplotypes derived from poor‐quality samples - Phillip A. Morin; Brenna R. Forester; Karin A. Forney; Carla A. Crossman; Brittany L. Hancock‐Hanser; Kelly M. Robertson; Lance G. Barrett‐Lennard; Robin W. Baird; John Calambokidis; Pat Gearin; M. Bradley Hanson; Cassie Schumacher; et al. (Molecular Ecology, 2021)
Harbor porpoise in the North Pacific are found in coastal waters from southern California to Japan, but population structure is poorly known outside of a few local areas. We used multiplexed amplicon sequencing of 292 loci and genotyped clusters of single nucleotide polymoirphisms as microhaplotypes ( N = 271 samples) in addition to mitochondrial (mtDNA) sequence data ( N = 413 samples) to examine the genetic structure from samples collected along the Pacific coast and inland waterways from California to southern British Columbia. We confirmed an overall pattern of strong isolation‐by‐distance, suggesting that individual dispersal is restricted. We also found evidence of regions where genetic differences are larger than expected based on geographical distance alone, implying current or historical barriers to gene flow. In particular, the southernmost population in California is genetically distinct ( F ST = 0.02 [microhaplotypes]; 0.31 [mtDNA]), with both reduced genetic variability and high frequency of an otherwise rare mtDNA haplotype. At the northern end of our study range, we found significant genetic differentiation of samples from the Strait of Georgia, previously identified as a potential biogeographical boundary or secondary contact zone between harbor porpoise populations. Association of microhaplotypes with remotely sensed environmental variables indicated potential local adaptation, especially at the southern end of the species’ range. These results inform conservation and management for this nearshore species, illustrate the value of genomic methods for detecting patterns of genetic structure within a continuously distributed marine species, and highlight the power of microhaplotype genotyping for detecting genetic structure in harbor porpoises despite reliance on poor‐quality samples.

Buffering effects of soil seed banks on plant community composition in response to land use and climate - Jan Plue; Hans Van Calster; Inger Auestad; Sofía Basto; Renée M. Bekker; Hans Henrik Bruun; Richard Chevalier; Guillaume Decocq; Ulf Grandin; Martin Hermy; Hans Jacquemyn; Anna Jakobsson; et al. (Global Ecology and Biogeography, 2021)
Aim Climate and land use are key determinants of biodiversity, with past and ongoing changes posing serious threats to global ecosystems. Unlike most other organism groups, plant species can possess dormant life‐history stages such as soil seed banks, which may help plant communities to resist or at least postpone the detrimental impact of global changes. This study investigates the potential for soil seed banks to achieve this. Location Europe. Time period 1978–2014. Major taxa studied Flowering plants. Methods Using a space‐for‐time/warming approach, we study plant species richness and composition in the herb layer and the soil seed bank in 2,796 community plots from 54 datasets in managed grasslands, forests and intermediate, successional habitats across a climate gradient. Results Soil seed banks held more species than the herb layer, being compositionally similar across habitats. Species richness was lower in forests and successional habitats compared to grasslands, with annual temperature range more important than mean annual temperature for determining richness. Climate and land‐use effects were generally less pronounced when plant community richness included seed bank species richness, while there was no clear effect of land use and climate on compositional similarity between the seed bank and the herb layer. Main conclusions High seed bank diversity and compositional similarity between the herb layer and seed bank plant communities may provide a potentially important functional buffer against the impact of ongoing environmental changes on plant communities. This capacity could, however, be threatened by climate warming. Dormant life‐history stages can therefore be important sources of diversity in changing environments, potentially underpinning already observed time‐lags in plant community responses to global change. However, as soil seed banks themselves appear, albeit less, vulnerable to the same changes, their potential to buffer change can only be temporary, and major community shifts may still be expected.

Cycling in degradation of organic polymers and uptake of nutrients by a litter‐degrading fungus - Aurin M. Vos; Robert‐Jan Bleichrodt; Koen C. Herman; Robin A. Ohm; Karin Scholtmeijer; Heike Schmitt; Luis G. Lugones; Han A. B. Wösten (Environmental Microbiology, 2021)
Summary Wood and litter degrading fungi are the main decomposers of lignocellulose and thus play a key role in carbon cycling in nature. Here, we provide evidence for a novel lignocellulose degradation strategy employed by the litter degrading fungus Agaricus bisporus (known as the white button mushroom). Fusion of hyphae allows this fungus to synchronize the activity of its mycelium over large distances (50 cm). The synchronized activity has a 13‐h interval that increases to 20 h before becoming irregular and it is associated with a 3.5‐fold increase in respiration, while compost temperature increases up to 2°C. Transcriptomic analysis of this burst‐like phenomenon supports a cyclic degradation of lignin, deconstruction of (hemi‐) cellulose and microbial cell wall polymers, and uptake of degradation products during vegetative growth of A. bisporus . Cycling in expression of the ligninolytic system, of enzymes involved in saccharification, and of proteins involved in nutrient uptake is proposed to provide an efficient way for degradation of substrates such as litter.

Correction to: Non-Invasive Multimodality Imaging Directly Shows TRPM4 Inhibition Ameliorates Stroke Reperfusion Injury - Bo Chen; Gandi Ng; Yahui Gao; See Wee Low; Edwin Sandanaraj; Boominathan Ramasamy; Sakthivel Sekar; Kishore Bhakoo; Tuck Wah Soong; Bernd Nilius; Carol Tang; Edward G. Robins; et al. (Translational Stroke Research, 2020)

Genetic analysis of maydis leaf blight resistance in subtropical maize (Zea mays L.) germplasm - B. Jeevan; Robin Gogoi; Devender Sharma; C. Manjunatha; H. Rajashekara; Dama Ram; K. K. Mishra; M. G. Mallikarjuna (Journal of Genetics, 2020)

Combined visual and biochemical analyses confirm depositor and diet for Neolithic coprolites from Skara Brae - Andrzej A. Romaniuk; Elsa Panciroli; Michael Buckley; Manasij Pal Chowdhury; Carla Willars; Jeremy S. Herman; Lore G. Troalen; Alexandra N. Shepherd; David V. Clarke; Alison Sheridan; Bart E. van Dongen; Ian B. Butler; et al. (Archaeological and Anthropological Sciences, 2020)
Coprolites (fossilized faeces) can provide valuable insights into species’ diet and related habits. In archaeozoological contexts, they are a potential source of information on human-animal interactions as well as human and animal subsistence. However, despite a broad discussion on coprolites in archaeology, such finds are rarely subject to detailed examination by researchers, perhaps due to the destructive nature of traditional analytical methods. Here, we have examined coprolitic remains from the Neolithic (third millennium BCE) settlement at Skara Brae, Orkney, using a range of modern methods: X-ray computed tomography, scanning electron microscopy, lipid and protein analysis (shotgun proteomics of the coprolite matrix as well as collagen peptide mass fingerprinting of isolated bone fragments). This combined approach minimised destructiveness of sampling, leaving sufficient material for subsequent study, while providing more information than traditional morphological examination alone. Based on gross visual examination, coprolites were predominantly attributed to domestic dogs ( Canis familiaris ), with morphologically identified bone inclusions derived from domestic sheep ( Ovis aries ) and common voles ( Microtus arvalis ). Partial dissection of a coprolite provided bone samples containing protein markers akin to those of domestic sheep. Considering the predominance of vertebral and distal limb bone fragments, Skara Brae dogs were probably consuming human butchery or meal refuse, either routinely fed to them or scavenged. The presumably opportunistic consumption of rodents may also have played a role in pest control.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Identification and Analysis of Nitrogen Dioxide Concentration for Air Quality Prediction Using Seasonal Autoregression Integrated with Moving Average - S. R. Mani Sekhar; G. M. Siddesh; Anjaneya Tiwari; Anay Khator; Robin Singh (Aerosol Science and Engineering, 2020)

The new kid on the block: immigrant males win big whereas females pay fitness cost after dispersal - April Robin Martinig; Andrew G. McAdam; Ben Dantzer; Jeffrey E. Lane; David W. Coltman; Stan Boutin (Ecology Letters, 2020)
Dispersal is nearly universal; yet, which sex tends to disperse more and their success thereafter depends on the fitness consequences of dispersal. We asked if lifetime fitness differed between residents and immigrants (successful between‐population dispersers) and their offspring using 29 years of monitoring from North American red squirrels ( Tamiasciurus hudsonicus ) in Canada. Compared to residents, immigrant females had 23% lower lifetime breeding success (LBS), while immigrant males had 29% higher LBS. Male immigration and female residency were favoured. Offspring born to immigrants had 15–43% lower LBS than offspring born to residents. We conclude that immigration benefitted males, but not females, which appeared to be making the best of a bad lot. Our results are in line with male‐biased dispersal being driven by local mate competition and local resource enhancement, while the intergenerational cost to immigration is a new complication in explaining the drivers of sex‐biased dispersal.

Co-eruptive tremor from Bogoslof volcano: seismic wavefield composition at regional distances - Matthew M. Haney; David Fee; Kathleen F. McKee; John J. Lyons; Robin S. Matoza; Aaron G. Wech; Gabrielle Tepp; Cheryl Searcy; T. Dylan Mikesell (Bulletin of Volcanology, 2020)

Facts, truths and myths about SPF shrimp in Aquaculture - Victoria Alday‐Sanz; James Brock; Timothy W. Flegel; Robins McIntosh; Melba G. Bondad‐Reantaso; Marcela Salazar; Rohana Subasinghe (Reviews in Aquaculture, 2020)
Shrimp domestication and genetic improvement programmes began in late 1980s, in the United States of America, under the United States Marine Shrimp Farming Program ( USMSFP ), using the Pacific whiteleg shrimp Penaeus vannamei . The USMSFP was based on proven concepts from the livestock and poultry industries and began with establishing a specific pathogen‐free ( SPF ) shrimp stock. The original shrimp stock was obtained using rigorous screening of captured wild shrimp for selection of individuals naturally free of major shrimp pathogens. Although the concept of SPF animals was well defined for terrestrial animals, it was relatively new for aquaculture, and it took some time to be adopted by the aquaculture community. In the early 1990s, parallel to USMSFP , several other programmes on genetic improvement of shrimp were also initiated in Latin America. Subsequently, several new terminologies and products, such as specific pathogen resistant ( SPR ) shrimp, specific pathogen tolerant ( SPT ) shrimp and even ‘all pathogen exposed’ ( APE ) shrimp, entered the shrimp industry vocabulary and became commercial. This led to confusion in the shrimp industry about the meaning, relationship and significance of these new terms with respect to SPF . This position paper attempts to clarify these concepts, provide science‐based definitions, reconfirms the importance of developing, maintaining and using domesticated, specific pathogen‐free ( SPF ) shrimp stocks (which may also achieve SPR and/or SPT status) to reduce the risk of disease outbreaks and increase production and profit. The same principles would apply to development of domesticated SPF stocks for other species used in aquaculture. The paper also discusses the difficulties of confirming and certifying SPF status due to the presence of endogenous viral elements ( EVE s) and calls for internationally agreed science and evidence‐based technical guidelines for producing healthy shrimp.

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Bioextractive Removal of Nitrogen by Oysters in Great Bay Piscataqua River Estuary, New Hampshire, USA - Suzanne B. Bricker; Raymond E. Grizzle; Philip Trowbridge; Julie M. Rose; Joao G. Ferreira; Katharine Wellman; Changbo Zhu; Eve Galimany; Gary H. Wikfors; Camille Saurel; Robin Landeck Miller; James Wands; et al. (Estuaries and Coasts, 2020)
Eutrophication is a challenge to coastal waters around the globe. In many places, nutrient reductions from land-based sources have not been sufficient to achieve desired water quality improvements. Bivalve shellfish have shown promise as an in-water strategy to complement land-based nutrient management. A local-scale production model was used to estimate oyster ( Crassostrea virginica ) harvest and bioextraction of nitrogen (N) in Great Bay Piscataqua River Estuary (GBP), New Hampshire, USA, because a system-scale ecological model was not available. Farm-scale N removal results (0.072 metric tons acre −1 year −1 ) were up-scaled to provide a system-wide removal estimate for current (0.61 metric tons year −1 ), and potential removal (2.35 metric tons year −1 ) at maximum possible expansion of licensed aquaculture areas. Restored reef N removal was included to provide a more complete picture. Nitrogen removal through reef sequestration was ~ 3 times that of aquaculture. Estimated reef-associated denitrification, based on previously reported rates, removed 0.19 metric tons N year −1 . When all oyster processes (aquaculture and reefs) were included, N removal was 0.33% and 0.54% of incoming N for current and expanded acres, respectively. An avoided cost approach, with wastewater treatment as the alternative management measure, was used to estimate the value of the N removed. The maximum economic value for aquaculture-based removal was $105,000 and $405,000 for current and expanded oyster areas, respectively. Combined aquaculture and reef restoration is suggested to maximize N reduction capacity while limiting use conflicts. Comparison of removal based on per oyster N content suggests much lower removal rates than model results, but model harvest estimates are similar to reported harvest. Though results are specific to GBP, the approach is transferable to estuaries that support bivalve aquaculture but do not have complex system-scale hydrodynamic or ecological models.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Is ‘re-mobilisation’ nature restoration or nature destruction? A commentary - Irene Delgado-Fernandez; Robin G. D. Davidson-Arnott; Patrick A. Hesp (Journal of Coastal Conservation, 2019)
Coastal dunes are experiencing increases in vegetation cover and reduced mobility levels in many sites around the world. Ecology-led approaches to coastal dune management perceive this change as ‘undesirable’ because the increase in plant cover leads to a reduction in partially vegetated to bare sand habitats and the species depending on them. This has generated a shift in the management paradigm where the objective is to revert this trend by intervening in the landscape, with actions ranging from re-introducing grazing and mowing, to mechanical removal of dune form and vegetation (dune ‘rejuvenation’). In some cases, such as many coastal dunes in Britain, this has also led to low controls on visitor pressure and allowing/promoting human trampling as a ‘natural’ way to free up areas of bare sand. This commentary critically analyses the main principles (and terminology) underlying this relatively recent shift in management paradigm, and questions assumptions such as ‘bare sand is good’ and/or ‘mobility is natural’ in the context of dune evolutionary cycles and responses to abiotic and biotic drivers. We review the limitations and dangers of this approach and argue that it is not sustainable given the current climatic and environmental conditions, and that it can increase the risk of coastal erosion and force dune systems to deviate from adapting and changing to direct/indirect drivers. Finally, we present the benefits of a management approach that focuses on minimizing human impacts so that natural processes continue to occur.

Economics of public health programs for underserved populations: a review of economic analysis of the National Breast and Cervical Cancer Early Detection Program - Jaya S. Khushalani; Justin G. Trogdon; Donatus U. Ekwueme; K. Robin Yabroff (Cancer Causes & Control, 2019)

Relationships Between Absolute and Relative Strength and Power in Male Police Officers of Varying Strength Levels - J. Jay Dawes; Robert G. Lockie; Charles L. Kornhauser; Ryan J. Holmes; Robin M. Orr (Journal of Science in Sport and Exercise, 2019)

Persistence of antibody response in chikungunya - Shweta Chelluboina; S. Robin; S. Aswathyraj; G. Arunkumar (VirusDisease, 2019)

Wake Characteristics of Tall Buildings in a Realistic Urban Canopy - Denise Hertwig; Hannah L. Gough; Sue Grimmond; Janet F. Barlow; Christoph W. Kent; William E. Lin; Alan G. Robins; Paul Hayden (Boundary-Layer Meteorology, 2019)

Experimental assessment of the biosafety of Trissolcus japonicus in New Zealand, prior to the anticipated arrival of the invasive pest Halyomorpha halys - J. G. Charles; G. A. Avila; Kim A. Hoelmer; Sophie Hunt; Robin Gardner-Gee; Frances MacDonald; Vicky Davis (BioControl, 2019)

Identification and characterization of a novel anti-inflammatory lipid isolated from Mycobacterium vaccae, a soil-derived bacterium with immunoregulatory and stress resilience properties - David G. Smith; Roberta Martinelli; Gurdyal S. Besra; Petr A. Illarionov; Istvan Szatmari; Peter Brazda; Mary A. Allen; Wenqing Xu; Xiang Wang; László Nagy; Robin D. Dowell; Graham A. W. Rook; et al. (Psychopharmacology, 2019)

Late Quaternary sea‐level change and evolution of Belfast Lough, Northern Ireland: new offshore evidence and implications for sea‐level reconstruction - Ruth M. K. Plets; S. Louise Callard; J. Andrew G. Cooper; Joseph T. Kelley; Daniel F. Belknap; Robin J. Edwards; Antony J. Long; Rory J. Quinn; Derek W. T. Jackson (Journal of Quaternary Science, 2019)
The interplay of eustatic and isostatic factors causes complex relative sea‐level (RSL) histories, particularly in paraglacial settings. In this context the past record of RSL is important in understanding ice‐sheet history, earth rheology and resulting glacio‐isostatic adjustment. Field data to develop sea‐level reconstructions are often limited to shallow depths and uncertainty exists as to the veracity of modelled sea‐level curves. We use seismic stratigraphy, 39 vibrocores and 26 radiocarbon dates to investigate the deglacial history of Belfast Lough, Northern Ireland, and reconstruct past RSL. A typical sequence of till, glacimarine and Holocene sediments is preserved. Two sea‐level lowstands (both max. −40 m) are recorded at c. 13.5 and 11.5k cal a bp . Each is followed by a rapid transgression and subsequent periods of RSL stability. The first transgression coincides temporally with a late stage of Meltwater Pulse 1a and the RSL stability occurred between c. 13.0 and c. 12.2k cal a bp (Younger Dryas). The second still/slowstand occurred between c. 10.3 and c. 11.5k cal a bp . Our data provide constraints on the direction and timing of RSL change during deglaciation. Application of the Depth of Closure concept adds an error term to sea‐level reconstructions based on seismic stratigraphic reconstructions.

Lifetime alcohol intake and pancreatic cancer incidence and survival: findings from the Melbourne Collaborative Cohort Study - Harindra Jayasekara; Dallas R. English; Allison M. Hodge; Robin Room; John L. Hopper; Roger L. Milne; Graham G. Giles; Robert J. MacInnis (Cancer Causes & Control, 2019)

Assessment of resistance to rice tungro disease in popular rice varieties in India by introgression of a transgene against Rice tungro bacilliform virus - G. Kumar; M. Jyothsna; P. Valarmathi; S. Roy; A. Banerjee; J. Tarafdar; B. K. Senapati; S. Robin; S. Manonmani; R. Rabindran; I. Dasgupta (Archives of Virology, 2019)

The emerging pathogen of chestnut Gnomoniopsis castaneae: the challenge posed by a versatile fungus - G. Lione; R. Danti; P. Fernandez-Conradi; J. V. Ferreira-Cardoso; F. Lefort; G. Marques; J. B. Meyer; S. Prospero; L. Radócz; C. Robin; T. Turchetti; A. M. Vettraino; et al. (European Journal of Plant Pathology, 2019)

Non-Invasive Multimodality Imaging Directly Shows TRPM4 Inhibition Ameliorates Stroke Reperfusion Injury - Bo Chen; Gandi Ng; Yahui Gao; See Wee Low; Edwin Sandanaraj; Boominathan Ramasamy; Sakthivel Sekar; Kishore Bhakoo; Tuck Wah Soong; Bernd Nilius; Carol Tang; Edward G. Robins; et al. (Translational Stroke Research, 2019)
The transient receptor potential melastatin 4 (TRPM4) channel has been suggested to play a key role in the treatment of ischemic stroke. However, in vivo evaluation of TRPM4 channel, in particular by direct channel suppression, is lacking. In this study, we used multimodal imaging to assess edema formation and quantify the amount of metabolically functional brain salvaged after a rat model of stroke reperfusion. TRPM4 upregulation in endothelium emerges as early as 2 h post-stroke induction. Expression of TRPM4 channel was suppressed directly in vivo by treatment with siRNA; scrambled siRNA was used as a control. T2-weighted MRI suggests that TRPM4 inhibition successfully reduces edema by 30% and concomitantly salvages functionally active brain, measured by 18 F-FDG-PET. These in vivo imaging results correlate well with post-mortem 2,3,5-triphenyltetrazolium chloride (TTC) staining which exhibits a 34.9% reduction in infarct volume after siRNA treatment. Furthermore, in a permanent stroke model, large areas of brain tissue displayed both edema and significant reductions in metabolic activity which was not shown in transient models with or without TRPM4 inhibition, indicating that tissue salvaged by TRPM4 inhibition during stroke reperfusion may survive. Evans Blue extravasation and hemoglobin quantification in the ipsilateral hemisphere were greatly reduced, suggesting that TRPM4 inhibition can improve BBB integrity after ischemic stroke reperfusion. Our results support the use of TRPM4 blocker for early stroke reperfusion.

Microplastic ingestion ubiquitous in marine turtles - Emily M. Duncan; Annette C. Broderick; Wayne J. Fuller; Tamara S. Galloway; Matthew H. Godfrey; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; Andrew G. Mayes; Lucy C. M. Omeyer; David Santillo; Robin T. E. Snape; et al. (Global Change Biology, 2019)
Despite concerns regarding the environmental impacts of microplastics, knowledge of the incidence and levels of synthetic particles in large marine vertebrates is lacking. Here, we utilize an optimized enzymatic digestion methodology, previously developed for zooplankton, to explore whether synthetic particles could be isolated from marine turtle ingesta. We report the presence of synthetic particles in every turtle subjected to investigation ( n = 102) which included individuals from all seven species of marine turtle, sampled from three ocean basins (Atlantic [ATL]: n = 30, four species; Mediterranean (MED): n = 56, two species; Pacific (PAC): n = 16, five species). Most particles ( n = 811) were fibres (ATL: 77.1% MED: 85.3% PAC: 64.8%) with blue and black being the dominant colours. In lesser quantities were fragments (ATL: 22.9%: MED: 14.7% PAC: 20.2%) and microbeads (4.8%; PAC only; to our knowledge the first isolation of microbeads from marine megavertebrates). Fourier transform infrared spectroscopy (FT‐IR) of a subsample of particles ( n = 169) showed a range of synthetic materials such as elastomers (MED: 61.2%; PAC: 3.4%), thermoplastics (ATL: 36.8%: MED: 20.7% PAC: 27.7%) and synthetic regenerated cellulosic fibres (SRCF; ATL: 63.2%: MED: 5.8% PAC: 68.9%). Synthetic particles being isolated from species occupying different trophic levels suggest the possibility of multiple ingestion pathways. These include exposure from polluted seawater and sediments and/or additional trophic transfer from contaminated prey/forage items. We assess the likelihood that microplastic ingestion presents a significant conservation problem at current levels compared to other anthropogenic threats.

Approaches to integrating genetic data into ecological networks - Elizabeth L. Clare; Aron J. Fazekas; Natalia V. Ivanova; Robin M. Floyd; Paul D. N. Hebert; Amanda M. Adams; Juliet Nagel; Rebecca Girton; Steven G. Newmaster; M. Brock Fenton (Molecular Ecology, 2019)
As molecular tools for assessing trophic interactions become common, research is increasingly focused on the construction of interaction networks. Here, we demonstrate three key methods for incorporating DNA data into network ecology and discuss analytical considerations using a model consisting of plants, insects, bats and their parasites from the Costa Rica dry forest. The simplest method involves the use of Sanger sequencing to acquire long sequences to validate or refine field identifications, for example of bats and their parasites, where one specimen yields one sequence and one identification. This method can be fully quantified and resolved and these data resemble traditional ecological networks. For more complex taxonomic identifications, we target multiple DNA loci, for example from a seed or fruit pulp sample in faeces. These networks are also well resolved but gene targets vary in resolution and quantification is difficult. Finally, for mixed templates such as faecal contents of insectivorous bats, we use DNA metabarcoding targeting two sequence lengths (157 and 407 bp) of one gene region and a MOTU, BLAST and BIN association approach to resolve nodes. This network type is complex to generate and analyse, and we discuss the implications of this type of resolution on network analysis. Using these data, we construct the first molecular‐based network of networks containing 3,304 interactions between 762 nodes of eight trophic functions and involving parasitic, mutualistic and predatory interactions. We provide a comparison of the relative strengths and weaknesses of these data types in network ecology.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Rapid warming is associated with population decline among terrestrial birds and mammals globally - Fiona E. B. Spooner; Richard G. Pearson; Robin Freeman (Global Change Biology, 2018)
Animal populations have undergone substantial declines in recent decades. These declines have occurred alongside rapid, human‐driven environmental change, including climate warming. An association between population declines and environmental change is well established, yet there has been relatively little analysis of the importance of the rates of climate warming and its interaction with conversion to anthropogenic land use in causing population declines. Here we present a global assessment of the impact of rapid climate warming and anthropogenic land use conversion on 987 populations of 481 species of terrestrial birds and mammals since 1950. We collated spatially referenced population trends of at least 5 years’ duration from the Living Planet database and used mixed effects models to assess the association of these trends with observed rates of climate warming, rates of conversion to anthropogenic land use, body mass, and protected area coverage. We found that declines in population abundance for both birds and mammals are greater in areas where mean temperature has increased more rapidly, and that this effect is more pronounced for birds. However, we do not find a strong effect of conversion to anthropogenic land use, body mass, or protected area coverage. Our results identify a link between rapid warming and population declines, thus supporting the notion that rapid climate warming is a global threat to biodiversity.

New records of the rare North American endemic Chara brittonii (Characeae), with comments on its distribution - Kenneth G. Karol; Mitchell S. Alix; Robin W. Scribailo; Paul M. Skawinski; Robin S. Sleith; Joseph A. Sardina; John D. Hall (Brittonia, 2018)

Ecological correlates of the spatial co‐occurrence of sympatric mammalian carnivores worldwide - Courtney L. Davis; Lindsey N. Rich; Zach J. Farris; Marcella J. Kelly; Mario S. Di Bitetti; Yamil Di Blanco; Sebastian Albanesi; Mohammad S. Farhadinia; Navid Gholikhani; Sandra Hamel; Bart J. Harmsen; Claudia Wultsch; et al. (Ecology Letters, 2018)
The composition of local mammalian carnivore communities has far‐reaching effects on terrestrial ecosystems worldwide. To better understand how carnivore communities are structured, we analysed camera trap data for 108 087 trap days across 12 countries spanning five continents. We estimate local probabilities of co‐occurrence among 768 species pairs from the order Carnivora and evaluate how shared ecological traits correlate with probabilities of co‐occurrence. Within individual study areas, species pairs co‐occurred more frequently than expected at random. Co‐occurrence probabilities were greatest for species pairs that shared ecological traits including similar body size, temporal activity pattern and diet. However, co‐occurrence decreased as compared to other species pairs when the pair included a large‐bodied carnivore. Our results suggest that a combination of shared traits and top‐down regulation by large carnivores shape local carnivore communities globally.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Progression of conventional hepatic cell culture models to bioengineered HepG2 cells for evaluation of herbal bioactivities - Pardeep Kaur; Robin; Rajendra G. Mehta; Saroj Arora; Balbir Singh (Biotechnology Letters, 2018)

Grapevine virus I, a putative new vitivirus detected in co-infection with grapevine virus G in New Zealand - Arnaud G. Blouin; Kar Mun Chooi; Ben Warren; Kathryn R. Napier; Roberto A. Barrero; Robin M. MacDiarmid (Archives of Virology, 2018)

The LEGATO cross-disciplinary integrated ecosystem service research framework: an example of integrating research results from the analysis of global change impacts and the social, cultural and economic system dynamics of irrigated rice production - Joachim H. Spangenberg; Alexis L. Beaurepaire; Erwin Bergmeier; Benjamin Burkhard; Ho Van Chien; Le Quoc Cuong; Christoph Görg; Volker Grescho; Le Huu Hai; Kong Luen Heong; Finbarr G. Horgan; Stefan Hotes; et al. (Paddy and Water Environment, 2018)

Scalar Fluxes Near a Tall Building in an Aligned Array of Rectangular Buildings - Vladimír Fuka; Zheng-Tong Xie; Ian P. Castro; Paul Hayden; Matteo Carpentieri; Alan G. Robins (Boundary-Layer Meteorology, 2018)

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Identification of a novel vitivirus from grapevines in New Zealand - Arnaud G. Blouin; Sandi Keenan; Kathryn R. Napier; Roberto A. Barrero; Robin M. MacDiarmid (Archives of Virology, 2018)

Non-targeted workflow for identification of antimicrobial compounds in animal feed using bioassay-directed screening in combination with liquid chromatography-high resolution mass spectrometry - Robin S. Wegh; Bjorn J. A. Berendsen; Wilma D. M. Driessen-Van Lankveld; Mariël G. Pikkemaat; Tina Zuidema; Leen A. Van Ginkel (Food Additives & Contaminants: Part A, 2017)

Opposing mechanisms affect taxonomic convergence between tree assemblages during tropical forest succession - Natalia Norden; Vanessa Boukili; Anne Chao; K. H. Ma; Susan G. Letcher; Robin L. Chazdon (Ecology Letters, 2017)
Whether successional forests converge towards an equilibrium in species composition remains an elusive question, hampered by high idiosyncrasy in successional dynamics. Based on long‐term tree monitoring in second‐growth ( SG ) and old‐growth ( OG ) forests in Costa Rica, we show that patterns of convergence between pairs of forest stands depend upon the relative abundance of species exhibiting distinct responses to the successional gradient. For instance, forest generalists contributed to convergence between SG and OG forests, whereas rare species and old‐growth specialists were a source of divergence. Overall, opposing trends in taxonomic similarity among different subsets of species nullified each other, producing a net outcome of stasis over time. Our results offer an explanation for the limited convergence observed between pairwise communities and suggest that rare species and old‐growth specialists may be prone to dispersal limitation, while the dynamics of generalists and second‐growth specialists are more predictable, enhancing resilience in tropical secondary forests.

Modelling small groundwater systems: experiences from the Braunton Burrows and Ainsdale coastal dune systems, UK - Corinna Abesser; Derek Clarke; Andrew G. Hughes; Nick S. Robins (Journal of Coastal Conservation, 2017)

Effects of progressive resistance training and weight loss versus weight loss alone on inflammatory and endothelial biomarkers in older adults with type 2 diabetes - Eliza G. Miller; Parneet Sethi; Caryl A. Nowson; David W. Dunstan; Robin M. Daly (European Journal of Applied Physiology, 2017)

Assessing global patterns in mammalian carnivore occupancy and richness by integrating local camera trap surveys - Lindsey N. Rich; Courtney L. Davis; Zach J. Farris; David A. W. Miller; Jody M. Tucker; Sandra Hamel; Mohammad S. Farhadinia; Robin Steenweg; Mario S. Di Bitetti; Kanchan Thapa; Mamadou D. Kane; S. Sunarto; et al. (Global Ecology and Biogeography, 2017)
Aim Biodiversity loss is a major driver of ecosystem change, yet the ecological data required to detect and mitigate losses are often lacking. Recently, camera trap surveys have been suggested as a method for sampling local wildlife communities, because these observations can be collated into a global monitoring network. To demonstrate the potential of camera traps for global monitoring, we assembled data from multiple local camera trap surveys to evaluate the interchange between fine‐ and broad‐scale processes impacting mammalian carnivore communities. Location Argentina, Belize, Botswana, Canada, Indonesia, Iran, Madagascar, Nepal, Norway, Senegal, South Africa, and the U.S.A. Methods We gathered camera trap data, totalling > 100,000 trap nights, from across five continents. To analyse local and species‐specific responses to anthropogenic and environmental variables, we fitted multispecies occurrence models to each study area. To analyse global‐level responses, we then fitted a multispecies, multi‐area occurrence model. Results We recorded 4,805 detections of 96 mammalian carnivore species photographed across 1,714 camera stations located in 12 countries. At the global level, our models revealed that carnivore richness and occupancy within study areas was positively associated with prey availability. Occupancy within study areas also tended to increase with greater protection and greater distances to roads. The strength of these relationships, however, differed among countries. Main conclusions We developed a research framework for leveraging global camera trap data to evaluate patterns of mammalian carnivore occurrence and richness across multiple spatial scales. Our research highlights the importance of intact prey populations and protected areas in conserving carnivore communities. Our research also highlights the potential of camera traps for monitoring wildlife communities and provides a case study for how this can be achieved on a global scale. We encourage greater integration and standardization among camera trap studies worldwide, which would help inform effective conservation planning for wildlife populations both locally and globally.

Neuronal oscillations and synchronicity associated with gamma-hydroxybutyrate during resting-state in healthy male volunteers - Robin von Rotz; Michael Kometer; Dario Dornbierer; Jürg Gertsch; M. Salomé Gachet; Franz X. Vollenweider; Erich Seifritz; Oliver G. Bosch; Boris B. Quednow (Psychopharmacology, 2017)

The population genetics of two orchid bees suggests high dispersal, low diploid male production and only an effect of island isolation in lowering genetic diversity - Antonella Soro; J. Javier G. Quezada-Euan; Panagiotis Theodorou; Robin F. A. Moritz; Robert J. Paxton (Conservation Genetics, 2017)

Demographic Drivers of Aboveground Biomass Dynamics During Secondary Succession in Neotropical Dry and Wet Forests - Danaë M. A. Rozendaal; Robin L. Chazdon; Felipe Arreola-Villa; Patricia Balvanera; Tony V. Bentos; Juan M. Dupuy; J. Luis Hernández-Stefanoni; Catarina C. Jakovac; Edwin E. Lebrija-Trejos; Madelon Lohbeck; Miguel Martínez-Ramos; Paulo E. S. Massoca; et al. (Ecosystems, 2017)

Effects of Elevated CO2 on the Swainsonine Chemotypes of Astragalus lentiginosus and Astragalus mollissimus - Daniel Cook; Dale R. Gardner; James A. Pfister; Clinton A. Stonecipher; Joseph G. Robins; Jack A. Morgan (Journal of Chemical Ecology, 2017)

The unseen invaders: introduced earthworms as drivers of change in plant communities in North American forests (a meta‐analysis) - Dylan Craven; Madhav P. Thakur; Erin K. Cameron; Lee E. Frelich; Robin Beauséjour; Robert B. Blair; Bernd Blossey; James Burtis; Amy Choi; Andrea Dávalos; Timothy J. Fahey; Nicholas A. Fisichelli; et al. (Global Change Biology, 2017)
Globally, biological invasions can have strong impacts on biodiversity as well as ecosystem functioning. While less conspicuous than introduced aboveground organisms, introduced belowground organisms may have similarly strong effects. Here, we synthesize for the first time the impacts of introduced earthworms on plant diversity and community composition in North American forests. We conducted a meta‐analysis using a total of 645 observations to quantify mean effect sizes of associations between introduced earthworm communities and plant diversity, cover of plant functional groups, and cover of native and non‐native plants. We found that plant diversity significantly declined with increasing richness of introduced earthworm ecological groups. While plant species richness or evenness did not change with earthworm invasion, our results indicate clear changes in plant community composition: cover of graminoids and non‐native plant species significantly increased, and cover of native plant species (of all functional groups) tended to decrease, with increasing earthworm biomass. Overall, these findings support the hypothesis that introduced earthworms facilitate particular plant species adapted to the abiotic conditions of earthworm‐invaded forests. Further, our study provides evidence that introduced earthworms are associated with declines in plant diversity in North American forests. Changing plant functional composition in these forests may have long‐lasting effects on ecosystem functioning.

A Generic Multi-Compartmental CNS Distribution Model Structure for 9 Drugs Allows Prediction of Human Brain Target Site Concentrations - Yumi Yamamoto; Pyry A. Välitalo; Dirk-Jan van den Berg; Robin Hartman; Willem van den Brink; Yin Cheong Wong; Dymphy R. Huntjens; Johannes H. Proost; An Vermeulen; Walter Krauwinkel; Suruchi Bakshi; Vincent Aranzana-Climent; et al. (Pharmaceutical Research, 2017)

Staying close to home? Genetic differentiation of rough-toothed dolphins near oceanic islands in the central Pacific Ocean - G. Renee Albertson; Robin W. Baird; Marc Oremus; M. Micahel Poole; Karen K. Martien; C. Scott Baker (Conservation Genetics, 2017)

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

Measurements and Computations of Flow in an Urban Street System - Ian P. Castro; Zheng-Tong Xie; V. Fuka; Alan G. Robins; M. Carpentieri; P. Hayden; D. Hertwig; O. Coceal (Boundary-Layer Meteorology, 2017)

Evaluation of the multiple biomarkers on identification of the vulnerable coastal pollution hotspots - G. Hariharan; R. Purvaja; R.S. Robin; R. Ramesh (Environmental Science and Pollution Research, 2016)

On the sustainability of inland fisheries: Finding a future for the forgotten - Steven J. Cooke; Edward H. Allison; T. Douglas Beard; Robert Arlinghaus; Angela H. Arthington; Devin M. Bartley; Ian G. Cowx; Carlos Fuentevilla; Nancy J. Leonard; Kai Lorenzen; Abigail J. Lynch; Vivian M. Nguyen; et al. (Ambio, 2016)

Is breast cancer risk associated with alcohol intake before first full-term pregnancy? - Harindra Jayasekara; Robert J. MacInnis; Allison M. Hodge; Robin Room; Roger L. Milne; John L. Hopper; Graham G. Giles; Dallas R. English (Cancer Causes & Control, 2016)

Evaluation of virus resistance and agronomic performance of rice cultivar ASD 16 after transfer of transgene against Rice tungro bacilliform virus by backcross breeding - P. Valarmathi; G. Kumar; S. Robin; S. Manonmani; I. Dasgupta; R. Rabindran (Virus Genes, 2016)

Context dependent bias in honeybee queen selection: swarm versus emergency queens - H. Michael G. Lattorff; Robin F. A. Moritz (Behavioral Ecology and Sociobiology, 2016)

Mercury Concentrations in Eggs of Red-Winged Blackbirds and Tree Swallows Breeding in Voyageurs National Park, Minnesota - Robin W. Tyser; Kristofer R. Rolfhus; James G. Wiener; Steve K. Windels; Thomas W. Custer; Paul M. Dummer (Archives of Environmental Contamination and Toxicology, 2016)

Liddle-Mutation of the β-Subunit, but not the γ-Subunit, Attenuates Protein Kinase C-Mediated Inhibition of Human Epithelial Sodium Channels (hENaC) - Gerard G. Robins; Geoffrey I. Sandle (The Journal of Membrane Biology, 2016)

How to Replicate the Functions and Biodiversity of a Threatened Tree Species? The Case of Fraxinus excelsior in Britain - Ruth J. Mitchell; Robin J. Pakeman; Alice Broome; Joan K. Beaton; Paul E. Bellamy; Rob W. Brooker; Chris J. Ellis; Alison J. Hester; Nick G. Hodgetts; Glenn R. Iason; Nick A. Littlewood; Gabor Pozsgai; et al. (Ecosystems, 2016)

Cultivar by environment effects of perennial ryegrass cultivars selected for high water soluble carbohydrates managed under differing precipitation levels - Joseph G. Robins; J. Alan Lovatt (Euphytica, 2016)

Down-regulation of Arabidopsis DND1 orthologs in potato and tomato leads to broad-spectrum resistance to late blight and powdery mildew - Kaile Sun; Anne-Marie A. Wolters; Annelies E. H. M. Loonen; Robin P. Huibers; René van der Vlugt; Aska Goverse; Evert Jacobsen; Richard G. F. Visser; Yuling Bai (Transgenic Research, 2016)

Identification and characterization of Fusarium spp. associated with root rots of field pea in North Dakota - Kishore Chittem; Febina M. Mathew; Matthew Gregoire; Robin S. Lamppa; Yen Wei Chang; Samuel G. Markell; Carl A. Bradley; Tharcisse Barasubiye; Rubella S. Goswami (European Journal of Plant Pathology, 2015)

Development and applications of a DNA labeling method with magnetic nanoparticles to study the role of horizontal gene transfer events between bacteria in soil pollutant bioremediation processes - J. Pivetal; M. Frénéa-Robin; N. Haddour; C. Vézy; L. F. Zanini; G. Ciuta; N. M. Dempsey; F. Dumas-Bouchiat; G. Reyne; S. Bégin-Colin; D. Felder-Flesh; C. Ghobril; et al. (Environmental Science and Pollution Research, 2015)

Variation in vervet (Chlorocebus aethiops) hair cortisol concentrations reflects ecological disturbance by humans - Nicolaas H. Fourie; Trudy R. Turner; Janine L. Brown; James D. Pampush; Joseph G. Lorenz; Robin M. Bernstein (Primates, 2015)

Impacts of Initial Fertilizers and Irrigation Systems on Paddy Methanogens and Methane Emission - Son G. Nguyen; Robin B. Guevarra; Jungman Kim; Cuong T. Ho; Mai V. Trinh; Tatsuya Unno (Water, Air, & Soil Pollution, 2015)

Heterosis for protein, digestibility, fiber, and water soluble carbohydrates in nine sources of orchardgrass germplasm - Joseph G. Robins; B. Shaun Bushman; Sandra Escribano; Kevin B. Jensen (Euphytica, 2015)

Analysis of swine fecal microbiota at various growth stages - Jungman Kim; Son G. Nguyen; Robin B. Guevarra; Iljoo Lee; Tatsuya Unno (Archives of Microbiology, 2015)

The effects of foundation species on community assembly: a global study on alpine cushion plant communities - Zaal Kikvidze; Robin W. Brooker; Bradley J. Butterfield; Ragan M. Callaway; Lohengrin A. Cavieres; Bradley J. Cook; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology, 2015)
Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze relationships between microhabitats and species diversity. Floristic dissimilarity did not change across biogeographic regions, but was consistently lower in the cushions than in the open microhabitat. Cushion plants appear to enable recruitment of many relatively stress‐intolerant species that otherwise would not establish in these communities, yet the niche space constructed by cushion plants supports a more homogeneous composition of species than the niche space beyond the cushion's influence. As a result, cushion plants support higher α‐diversity and a larger species pool, but harbor assemblies with lower β‐diversity than open microhabitats. We conclude that habitats with and without dominant foundation species can strongly differ in the processes that drive species recruitment, and thus the relationship between local and regional species diversity.

Distribution of Nitellopsis obtusa (Characeae) in New York, U.S.A. - Robin S. Sleith; Amy J. Havens; Robert A. Stewart; Kenneth G. Karol (Brittonia, 2015)

Time is of the essence: an application of a relational event model for animal social networks - K. P. Patison; E. Quintane; D. L. Swain; G. Robins; P. Pattison (Behavioral Ecology and Sociobiology, 2015)

Development of Action Thresholds for Management of Bactericera cockerelli and Zebra Chip Disease in Potatoes at Pukekohe, New Zealand - Graham P. Walker; Frances H. MacDonald; Peter J. Wright; Aleise J. Puketapu; Robin Gardner-Gee; Patrick G. Connolly; John A. D. Anderson (American Journal of Potato Research, 2015)

Lifetime alcohol consumption and upper aero-digestive tract cancer risk in the Melbourne Collaborative Cohort Study - Harindra Jayasekara; Robert J. MacInnis; Allison M. Hodge; John L. Hopper; Graham G. Giles; Robin Room; Dallas R. English (Cancer Causes & Control, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson - Ben H. Warren; Daniel Simberloff; Robert E. Ricklefs; Robin Aguilée; Fabien L. Condamine; Dominique Gravel; Hélène Morlon; Nicolas Mouquet; James Rosindell; Juliane Casquet; Elena Conti; Josselin Cornuault; et al. (Ecology Letters, 2015)
The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, ‘An equilibrium theory of insular zoogeography’, was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.

Refinement of schizophrenia GWAS loci using methylome-wide association data - Gaurav Kumar; Shaunna L. Clark; Joseph L. McClay; Andrey A. Shabalin; Daniel E. Adkins; Linying Xie; Robin Chan; Srilaxmi Nerella; Yunjung Kim; Patrick F. Sullivan; Christina M. Hultman; Patrik K. E. Magnusson; et al. (Human Genetics, 2015)

Activation tagging of ATHB13 in Arabidopsis thaliana confers broad-spectrum disease resistance - Dongli Gao; Michela Appiano; Robin P. Huibers; Xi Chen; Annelies E. H. M. Loonen; Richard G. F. Visser; Anne -Marie A. Wolters; Yuling Bai (Plant Molecular Biology, 2014)

Calcium Rapidly Down-Regulates Human Renal Epithelial Sodium Channels Via a W-7-Sensitive Mechanism - Gerard G. Robins; Geoffrey I. Sandle (The Journal of Membrane Biology, 2014)

Biodiversity patterns of nutrient-rich fish ponds and implications for conservation - A. Wezel; B. Oertli; V. Rosset; F. Arthaud; B. Leroy; R. Smith; S. Angélibert; G. Bornette; D. Vallod; J. Robin (Limnology, 2014)

Statistical properties of concentration fluctuations in two merging plumes - D. Contini; A. G. Robins; P. Hayden (Environmental Fluid Mechanics, 2014)

Thermal physiology and species distribution models reveal climate vulnerability of temperate amphibians - Alyssa A. Gerick; Robin G. Munshaw; Wendy J. Palen; Stacey A. Combes; Sacha M. O'Regan (Journal of Biogeography, 2014)
Aim High‐latitude ectotherms are predicted to be less physiologically vulnerable to climate warming than tropical species based on their larger thermal safety margins, the distance between ambient temperatures and species' thermal optima. We sought to test the prediction that high latitude amphibians are buffered against the impacts of climate warming. Location British Columbia, Canada. Methods We estimated the risk from climate change for three high‐latitude amphibian species ( Spea intermontana , Rana aurora and Pseudacris regilla ) by combining thermal performance experiments with species distribution models and predicted changes in maximum summer temperatures through the 2080s, in order to demonstrate temporal and geographical trends in vulnerability to climate warming among and within species. Results We found that species have thermal safety margins of 3.2–3.8 °C based on current maximum summer temperatures. However, by the 2080s (emissions scenario A1B), we estimate that 45–82% of our focal species' current distributions will experience maximum summer temperatures above their thermal optima. We also found that by using long‐term average temperatures, as some studies have done, there were almost no scenarios in which populations of any species were experiencing temperatures greater than their thermal optima. Main conclusions Combining spatially explicit species distribution models with performance physiology allows us to predict where limiting temperatures will occur in the coming decades, and can guide climate mitigation and conservation efforts before populations decline. Despite moderate thermal safety margins, high‐latitude ectotherms can be highly vulnerable to climate warming when spatio‐temporal variation is incorporated into estimates of risk as a result of climate change.

Full Recovery from a Potentially Lethal Dose of Mercuric Chloride - D. Michael G. Beasley; Leo J. Schep; Robin J. Slaughter; Wayne A. Temple; Jonathan M. Michel (Journal of Medical Toxicology, 2014)

Checklist for standardized reporting of drug–drug interaction management guidelines - Annemieke Floor-Schreudering; Arjen F. J. Geerts; Jeffrey K. Aronson; Marcel L. Bouvy; Robin E. Ferner; Peter A. G. M. De Smet (European Journal of Clinical Pharmacology, 2014)

Preliminary findings of cortical thickness abnormalities in blast injured service members and their relationship to clinical findings - D. F. Tate; G. E. York; M. W. Reid; D. B. Cooper; L. Jones; D. A. Robin; J. E. Kennedy; J. Lewis (Brain Imaging and Behavior, 2014)

Biodiversity in eutrophicated shallow lakes: determination of tipping points and tools for monitoring - J. Robin; A. Wezel; G. Bornette; F. Arthaud; S. Angélibert; V. Rosset; B. Oertli (Hydrobiologia, 2014)

Transgenic upregulation of the condensed tannin pathway in poplar leads to a dramatic shift in leaf palatability for two tree-feeding Lepidoptera - G. Andreas Boeckler; Megan Towns; Sybille B. Unsicker; Robin D. Mellway; Lynn Yip; Ines Hilke; Jonathan Gershenzon; C. Peter Constabel (Journal of Chemical Ecology, 2014)

A reporter based single step assay for evaluation of inhibitors targeting HIV-1 Rev–RRE interaction - Sumeer Raina; Ajit G. Chande; Masanori Baba; Robin Mukhopadhyaya (VirusDisease, 2014)

Ovarian Cancer: Deaf and Hearing Women’s Knowledge Before and After an Educational Video - Lindsay G. Jensen; Melanie Nakaji; Kadie M. Harry; Nick Gallegos; Vanessa L. Malcarne; Georgia Robins Sadler (Journal of Cancer Education, 2013)

Rapid stimulation of human renal ENaC by cAMP in Xenopus laevis oocytes - G. G. Robins; K. A. MacLennan; R. P. Boot-Handford; G. I. Sandle (Journal of Physiology and Biochemistry, 2013)

DTI tractography and white matter fiber tract characteristics in euthymic bipolar I patients and healthy control subjects - Carinna M. Torgerson; Andrei Irimia; Alex D. Leow; George Bartzokis; Teena D. Moody; Robin G. Jennings; Jeffry R. Alger; John Darrell Van Horn; Lori L. Altshuler (Brain Imaging and Behavior, 2013)

The blue light receptor complex WC ‐1/2 of S chizophyllum commune is involved in mushroom formation and protection against phototoxicity - Robin A. Ohm; David Aerts; Han A. B. Wösten; Luis G. Lugones (Environmental Microbiology, 2013)
Summary Blue light is necessary for initiation of mushroom formation in S chizophyllum commune . The genome of this basidiomycete contains homologues of the blue light receptor genes wc‐1 and wc‐2 of N eurospora crassa . Here, it is shown that inactivation of either or both of these genes in S . commune results in a blind phenotype. Mushroom formation was abolished in dikaryons and they formed symmetrical instead of asymmetrical colonies. Development was restored in a temperature dependent way in a Δ wc‐2 Δ wc‐2 strain by introducing a construct encompassing the wc‐2 gene under control of the promoter of the heat shock gene hsp3 . A genome‐wide expression analysis showed that the transcription factor genes c2h2 and hom1 as well as many hydrophobin genes are downregulated in light‐grown colonies of the Δ wc‐2 Δ wc‐2 mutant when compared with the wild‐type dikaryon. Inactivation of wc‐1 and/or wc‐2 also resulted in sensitivity of the mycelium to intense light. Monokaryotic mutant strains only survived exposure to 6500 lux of light by growing into the agar. Expression analysis indicates that the photosensitivity of the Δ wc‐1 and Δ wc‐2 strains is due to lower levels of photolyase and ferrochelatase.

Dry matter yield combining ability among nine sources of orchardgrass germplasm - Joseph G. Robins; B. Shaun Bushman; Kevin B. Jensen (Euphytica, 2012)

Corrigendum - CLARE D. MARSDEN; ROSIE WOODROFFE; MICHAEL G. L. MILLS; J. WELDON MCNUTT; SCOTT CREEL; ROSEMARY GROOM; MASENGA EMMANUEL; SARAH CLEAVELAND; PIETER KAT; GREGORY S. A. RASMUSSEN; JOSHUA GINSBERG; ROBIN LINES; et al. (Molecular Ecology, 2012)

The chestnut blight fungus world tour: successive introduction events from diverse origins in an invasive plant fungal pathogen - C. DUTECH; B. BARRÈS; J. BRIDIER; C. ROBIN; M. G. MILGROOM; V. RAVIGNÉ (Molecular Ecology, 2012)
Clonal expansion has been observed in several invasive fungal plant pathogens colonizing new areas, raising the question of the origin of clonal lineages. Using microsatellite markers, we retraced the evolutionary history of introduction of the chestnut blight fungus, Cryphonectria parasitica , in North America and western Europe. Combining discriminant analysis of principal components and approximate Bayesian computation analysis, we showed that several introduction events from genetically differentiated source populations have occurred in both invaded areas. In addition, a low signal of genetic recombination among different source populations was suggested in North America. Finally, two genetic lineages were present in both invaded areas as well as in the native areas, suggesting the existence of genetic lineages with a high capacity to establish in diverse environments and host species. This study confirmed the importance of multiple introductions, but questioned the role of genetic admixture in the success of introduction of a fungal plant pathogen.

Demographic drivers of successional changes in phylogenetic structure across life‐history stages in plant communities - Natalia Norden; Susan G. Letcher; Vanessa Boukili; Nathan G. Swenson; Robin Chazdon (Ecology, 2012)
To gain insight into the ecological processes driving community reassembly in disturbed ecosystems, we assessed the phylogenetic dispersion of early‐ and late‐successional tree species occurring in lowland forests of northeastern Costa Rica. Early‐successional species were more closely related than expected by chance, whereas late‐successional species tended to be less closely related than expected by chance. Then, we evaluated temporal changes in the phylogenetic structure of seedling and tree assemblages in four 1‐ha plots of secondary forests in this region. We found an increase in the phylogenetic evenness among tree individuals over time in all secondary tree assemblages, indicating that relatedness among tree individuals decreases as succession unfolds. This pattern was jointly promoted by recruitment and mortality processes, suggesting that increasing evenness was caused by the replacement of individuals of early‐successional species from closely related lineages by late‐successional species belonging to a wider diversity of lineages. Based on species occurrence, however, tree community reassembly did not show any significant phylogenetic trend over time. These results suggest that shifts in species abundance over succession have a greater impact on the phylogenetic structure of the community than the turnover of species. Seedling assemblages showed higher phylogenetic evenness than tree assemblages, suggesting that propagule colonization is an important process driving phylogenetic changes in species composition throughout succession. Overall, our findings showed that the phylogenetic structure of these successional communities varies at two temporal scales. At short timescales, decreased dominance by early‐successional species over succession leads to increased evenness among tree individuals. At longer timescales, colonization processes result in increased phylogenetic evenness in seedling communities compared to tree communities, forecasting increasing phylogenetic evenness among adult individuals at late‐successional stages.

An Inverse Method for Determining Source Characteristics for Emergency Response Applications - A. C. Rudd; A. G. Robins; J. J. Lepley; S. E. Belcher (Boundary-Layer Meteorology, 2012)

Phylogenetic diversity and the functioning of ecosystems - Diane S. Srivastava; Marc W. Cadotte; A. Andrew M. MacDonald; Robin G. Marushia; Nicholas Mirotchnick (Ecology Letters, 2012)
Phylogenetic diversity ( PD ) describes the total amount of phylogenetic distance among species in a community. Although there has been substantial research on the factors that determine community PD , exploration of the consequences of PD for ecosystem functioning is just beginning. We argue that PD may be useful in predicting ecosystem functions in a range of communities, from single‐trophic to complex networks. Many traits show a phylogenetic signal, suggesting that PD can estimate the functional trait space of a community, and thus ecosystem functioning. Phylogeny also determines interactions among species, and so could help predict how extinctions cascade through ecological networks and thus impact ecosystem functions. Although the initial evidence available suggests patterns consistent with these predictions, we caution that the utility of PD depends critically on the strength of phylogenetic signals to both traits and interactions. We advocate for a synthetic approach that incorporates a deeper understanding of how traits and interactions are shaped by evolution, and outline key areas for future research. If these complexities can be incorporated into future studies, relationships between PD and ecosystem function bear promise in conceptually unifying evolutionary biology with ecosystem ecology.

A functional screen for recovery of 4′‐phosphopantetheinyl transferase and associated natural product biosynthesis genes from metagenome libraries - J. G. Owen; K. J. Robins; N. S. Parachin; D. F. Ackerley (Environmental Microbiology, 2012)
Summary The single‐module non‐ribosomal peptide synthetase BpsA from Streptomyces lavendulae has the unique ability to autonomously synthesize a coloured product (indigoidine) from a single substrate ( l ‐glutamine), conditional upon activation by a 4′‐phosphopantetheinyl transferase (PPTase) partner. We show that bpsA can be expressed in an entD PPTase gene deleted mutant of Escherichia coli to yield a sensitive reporter strain for recovery of PPTase genes from metagenome libraries. We also show that recombinant bpsA constructs, generated by substitution of the native peptidyl carrier protein domain followed by directed evolution to restore function, can be used to increase the diversity of PPTase genes recovered from a sample. As PPTases are essential for activation of non‐ribosomal peptide synthetase and polyketide synthase enzymes, they are frequently associated with secondary metabolite gene clusters. Nearly half of the PPTases recovered in our screening of two small‐insert soil metagenome libraries were genetically linked to recognizable secondary metabolite biosynthetic genes, demonstrating that PPTase‐targeting functional screens can be used for efficient recovery of natural product gene clusters from metagenome libraries. The plasticity and portability of bpsA reporter genes can potentially be exploited to maximize recovery and expression of PPTase‐bearing clones in a wide range of hosts.

Detection and characterisation of two novel vitiviruses infecting Actinidia - Arnaud G. Blouin; Ramesh R. Chavan; Michael N. Pearson; Robin M. MacDiarmid; Daniel Cohen (Archives of Virology, 2012)

Alcohol-induced psychotic disorder: brain perfusion and psychopathology—before and after anti-psychotic treatment - Gerhard P. Jordaan; James M. Warwick; Daan G. Nel; Richard Hewlett; Robin Emsley (Metabolic Brain Disease, 2012)

Relationships among seed quality characteristics in a collection of western wheatgrass germplasms - Joseph G. Robins; Kishor Bhattarai; B. Shaun Bushman; Steven R. Larson (Euphytica, 2012)

Seasonal and Annual Fluxes of Nutrients and Organic Matter from Large Rivers to the Arctic Ocean and Surrounding Seas - Robert Max Holmes; James W. McClelland; Bruce J. Peterson; Suzanne E. Tank; Ekaterina Bulygina; Timothy I. Eglinton; Viacheslav V. Gordeev; Tatiana Y. Gurtovaya; Peter A. Raymond; Daniel J. Repeta; Robin Staples; Robert G. Striegl; et al. (Estuaries and Coasts, 2012)

Spatial and temporal patterns of neutral and adaptive genetic variation in the endangered African wild dog ( Lycaon pictus ) - CLARE D. MARSDEN; ROSIE WOODROFFE; MICHAEL G. L. MILLS; J. WELDON McNUTT; SCOTT CREEL; ROSEMARY GROOM; MASENGA EMMANUEL; SARAH CLEAVELAND; PIETER KAT; GREGORY S.A. RASMUSSEN; JOSHUA GINSBERG; ROBIN LINES; et al. (Molecular Ecology, 2012)
Deciphering patterns of genetic variation within a species is essential for understanding population structure, local adaptation and differences in diversity between populations. Whilst neutrally evolving genetic markers can be used to elucidate demographic processes and genetic structure, they are not subject to selection and therefore are not informative about patterns of adaptive variation. As such, assessments of pertinent adaptive loci, such as the immunity genes of the major histocompatibility complex (MHC), are increasingly being incorporated into genetic studies. In this study, we combined neutral (microsatellite, mtDNA) and adaptive (MHC class II DLA‐DRB1 locus) markers to elucidate the factors influencing patterns of genetic variation in the African wild dog ( Lycaon pictus ); an endangered canid that has suffered extensive declines in distribution and abundance. Our genetic analyses found all extant wild dog populations to be relatively small ( N e

Publication Bias in Neuroimaging Research: Implications for Meta-Analyses - Robin G. Jennings; John D. Van Horn (Neuroinformatics, 2012)

Ectomycorrhizal symbiosis of tropical African trees - Amadou M. Bâ; Robin Duponnois; Bernard Moyersoen; Abdala G. Diédhiou (Mycorrhiza, 2012)

Species-Specific Chemical Signatures in Scale Insect Honeydew - Manpreet K. Dhami; Robin Gardner-Gee; Jeremy Van Houtte; Silas G. Villas-Bôas; Jacqueline R. Beggs (Journal of Chemical Ecology, 2011)

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

An Unusual Case of Relay Pentobarbital Toxicosis in a Dog - Karyn Bischoff; Robin Jaeger; Joseph G. Ebel (Journal of Medical Toxicology, 2011)

Orchardgrass (Dactylis glomerata L.) EST and SSR marker development, annotation, and transferability - B. Shaun Bushman; Steve R. Larson; Metin Tuna; Mark S. West; Alvaro G. Hernandez; Deepika Vullaganti; George Gong; Joseph G. Robins; Kevin B. Jensen; Jyothi Thimmapuram (Theoretical and Applied Genetics, 2011)

Late Miocene lacustrine sedimentation in the Mytilinii Basin, Samos Island, Greece - R. Bernhart Owen; Robin W. Renaut; Michael G. Stamatakis (Journal of Paleolimnology, 2011)

Genetic discontinuity among regional populations of Lophelia pertusa in the North Atlantic Ocean - Cheryl L. Morrison; Steve W. Ross; Martha S. Nizinski; Sandra Brooke; Johanna Järnegren; Rhian G. Waller; Robin L. Johnson; Tim L. King (Conservation Genetics, 2011)

A novel statistical method for classifying habitat generalists and specialists - Robin L. Chazdon; Anne Chao; Robert K. Colwell; Shang-Yi Lin; Natalia Norden; Susan G. Letcher; David B. Clark; Bryan Finegan; J. Pablo Arroyo (Ecology, 2011)
We develop a novel statistical approach for classifying generalists and specialists in two distinct habitats. Using a multinomial model based on estimated species relative abundance in two habitats, our method minimizes bias due to differences in sampling intensities between two habitat types as well as bias due to insufficient sampling within each habitat. The method permits a robust statistical classification of habitat specialists and generalists, without excluding rare species a priori. Based on a user‐defined specialization threshold, the model classifies species into one of four groups: (1) generalist; (2) habitat A specialist; (3) habitat B specialist; and (4) too rare to classify with confidence. We illustrate our multinomial classification method using two contrasting data sets: (1) bird abundance in woodland and heath habitats in southeastern Australia and (2) tree abundance in second‐growth (SG) and old‐growth (OG) rain forests in the Caribbean lowlands of northeastern Costa Rica. We evaluate the multinomial model in detail for the tree data set. Our results for birds were highly concordant with a previous nonstatistical classification, but our method classified a higher fraction (57.7%) of bird species with statistical confidence. Based on a conservative specialization threshold and adjustment for multiple comparisons, 64.4% of tree species in the full sample were too rare to classify with confidence. Among the species classified, OG specialists constituted the largest class (40.6%), followed by generalist tree species (36.7%) and SG specialists (22.7%). The multinomial model was more sensitive than indicator value analysis or abundance‐based phi coefficient indices in detecting habitat specialists and also detects generalists statistically. Classification of specialists and generalists based on rarefied subsamples was highly consistent with classification based on the full sample, even for sampling percentages as low as 20%. Major advantages of the new method are (1) its ability to distinguish habitat generalists (species with no significant habitat affinity) from species that are simply too rare to classify and (2) applicability to a single representative sample or a single pooled set of representative samples from each of two habitat types. The method as currently developed can be applied to no more than two habitats at a time.

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

New tools to boost butterfly habitat quality in existing grass buffer strips - Robin J. Blake; Ben A. Woodcock; Duncan B. Westbury; Peter Sutton; Simon G. Potts (Journal of Insect Conservation, 2011)

Social parasitism of queens and workers in the Cape honeybee (Apis mellifera capensis) - Robin F. A. Moritz; H. Michael G. Lattorff; Kendall L. Crous; Randall H. Hepburn (Behavioral Ecology and Sociobiology, 2011)

Application of a coastal model to simulate present and future inundation and aid coastal management - Peter E. Robins; Alan G. Davies; Rod Jones (Journal of Coastal Conservation, 2011)

Correlations Between Gene Expression and Mercury Levels in Blood of Boys With and Without Autism - Boryana Stamova; Peter G. Green; Yingfang Tian; Irva Hertz-Picciotto; Isaac N. Pessah; Robin Hansen; Xiaowei Yang; Jennifer Teng; Jeffrey P. Gregg; Paul Ashwood; Judy Van de Water; Frank R. Sharp (Neurotoxicity Research, 2011)

Correlations of Gene Expression with Blood Lead Levels in Children with Autism Compared to Typically Developing Controls - Yingfang Tian; Peter G. Green; Boryana Stamova; Irva Hertz-Picciotto; Isaac N. Pessah; Robin Hansen; Xiaowei Yang; Jeffrey P. Gregg; Paul Ashwood; Glen Jickling; Judy Van de Water; Frank R. Sharp (Neurotoxicity Research, 2011)

Trait similarity, shared ancestry and the structure of neighbourhood interactions in a subtropical wet forest: implications for community assembly - María Uriarte; Nathan G. Swenson; Robin L. Chazdon; Liza S. Comita; W. John Kress; David Erickson; Jimena Forero‐Montaña; Jess K. Zimmerman; Jill Thompson (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1503–1514 Abstract The phylogenetic structure and distribution of functional traits in a community can provide insights into community assembly processes. However, these insights are sensitive to the spatial scale of analysis. Here, we use spatially explicit, neighbourhood models of tree growth and survival for 19 tree species, a highly resolved molecular phylogeny and information on eight functional traits to quantify the relative efficacy of functional similarity and shared ancestry in describing the effects of spatial interactions between tree species on demographic rates. We also assess the congruence of these results with observed phylogenetic and functional structure in the neighbourhoods of live and dead trees. We found strong support for models in which the effects of spatial neighbourhood interactions on tree growth and survival were scaled to species‐specific mean functional trait values (e.g., wood specific gravity, leaf succulence and maximum height) but not to phylogenetic distance. The weak phylogenetic signal in functional trait data allowed us to independently interpret the static neighbourhood functional and phylogenetic patterns. We observed greater functional trait similarity in the neighbourhoods of live trees relative to those of dead trees suggesting that environmental filtering is the major force structuring this tree community at this scale while competitive interactions play a lesser role.

An efficient gene deletion procedure for the mushroom-forming basidiomycete Schizophyllum commune - Robin A. Ohm; Jan F. de Jong; Elsa Berends; Fengfeng Wang; Han A. B. Wösten; Luis G. Lugones (World Journal of Microbiology and Biotechnology, 2010)

Trace elements and cathodoluminescence of quartz in stockwork veins of Mongolian porphyry-style deposits - Axel Müller; Richard Herrington; Robin Armstrong; Reimar Seltmann; Douglas J. Kirwin; Nina G. Stenina; Andreas Kronz (Mineralium Deposita, 2010)

Divergent composition but similar function of soil food webs of individual plants: plant species and community effects - T. M. Bezemer; M. T. Fountain; J. M. Barea; S. Christensen; S. C. Dekker; H. Duyts; R. van Hal; J. A. Harvey; K. Hedlund; M. Maraun; J. Mikola; A. G. Mladenov; et al. (Ecology, 2010)
Soils are extremely rich in biodiversity, and soil organisms play pivotal roles in supporting terrestrial life, but the role that individual plants and plant communities play in influencing the diversity and functioning of soil food webs remains highly debated. Plants, as primary producers and providers of resources to the soil food web, are of vital importance for the composition, structure, and functioning of soil communities. However, whether natural soil food webs that are completely open to immigration and emigration differ underneath individual plants remains unknown. In a biodiversity restoration experiment we first compared the soil nematode communities of 228 individual plants belonging to eight herbaceous species. We included grass, leguminous, and non‐leguminous species. Each individual plant grew intermingled with other species, but all plant species had a different nematode community. Moreover, nematode communities were more similar when plant individuals were growing in the same as compared to different plant communities, and these effects were most apparent for the groups of bacterivorous, carnivorous, and omnivorous nematodes. Subsequently, we analyzed the composition, structure, and functioning of the complete soil food webs of 58 individual plants, belonging to two of the plant species, Lotus corniculatus (Fabaceae) and Plantago lanceolata (Plantaginaceae). We isolated and identified more than 150 taxa/groups of soil organisms. The soil community composition and structure of the entire food webs were influenced both by the species identity of the plant individual and the surrounding plant community. Unexpectedly, plant identity had the strongest effects on decomposing soil organisms, widely believed to be generalist feeders. In contrast, quantitative food web modeling showed that the composition of the plant community influenced nitrogen mineralization under individual plants, but that plant species identity did not affect nitrogen or carbon mineralization or food web stability. Hence, the composition and structure of entire soil food webs vary at the scale of individual plants and are strongly influenced by the species identity of the plant. However, the ecosystem functions these food webs provide are determined by the identity of the entire plant community.

In-Street Wind Direction Variability in the Vicinity of a Busy Intersection in Central London - Ahmed A. Balogun; Alison S. Tomlin; Curtis R. Wood; Janet F. Barlow; Stephen E. Belcher; Robert J. Smalley; Justin J. N. Lingard; Sam J. Arnold; Adrian Dobre; Alan G. Robins; Damien Martin; Dudley E. Shallcross (Boundary-Layer Meteorology, 2010)

Placement of attine ant-associated Pseudonocardia in a global Pseudonocardia phylogeny (Pseudonocardiaceae, Actinomycetales): a test of two symbiont-association models - Ulrich G. Mueller; Heather Ishak; Jung C. Lee; Ruchira Sen; Robin R. Gutell (Antonie van Leeuwenhoek, 2010)

Erratum to: Nestmate Recognition and the Role of Cuticular Hydrocarbons in the African Termite Raiding Ant Pachycondyla analis - Abdullahi A. Yusuf; Christian W. W. Pirk; Robin M. Crewe; Peter G. N. Njagi; Ian Gordon; Baldwyn Torto (Journal of Chemical Ecology, 2010)

Morphological controls in sandy estuaries: the influence of tidal flats and bathymetry on sediment transport - Peter Edward Robins; Alan G. Davies (Ocean Dynamics, 2010)

Phylogenetic network of Linum species as revealed by non-coding chloroplast DNA sequences - Yong-Bi Fu; Robin G. Allaby (Genetic Resources and Crop Evolution, 2010)

Fish Migration, Dams, and Loss of Ecosystem Services in the Mekong Basin - Patrick J. Dugan; Chris Barlow; Angelo A. Agostinho; Eric Baran; Glenn F. Cada; Daqing Chen; Ian G. Cowx; John W. Ferguson; Tuantong Jutagate; Martin Mallen-Cooper; Gerd Marmulla; John Nestler; et al. (Ambio, 2010)

Tracer Flux Balance at an Urban Canyon Intersection - Matteo Carpentieri; Alan G. Robins (Boundary-Layer Meteorology, 2010)

Impacts of the invasive plant Fallopia japonica (Houtt.) on plant communities and ecosystem processes - Anna G. Aguilera; Peter Alpert; Jeffrey S. Dukes; Robin Harrington (Biological Invasions, 2010)

Nestmate Recognition and the Role of Cuticular Hydrocarbons in the African Termite Raiding Ant Pachycondyla analis - Abdullahi A. Yusuf; Christian W. W. Pirk; Robin M. Crewe; Peter G. N. Njagi; Ian Gordon; Baldwyn Torto (Journal of Chemical Ecology, 2010)

A simulation of the effect of inbreeding on crop domestication genetics with comments on the integration of archaeobotany and genetics: a reply to Honne and Heun - Robin G. Allaby; Terence A. Brown; Dorian Q. Fuller (Vegetation History and Archaeobotany, 2010)

Three-Dimensional Mapping of Air Flow at an Urban Canyon Intersection - Matteo Carpentieri; Alan G. Robins; Sandro Baldi (Boundary-Layer Meteorology, 2009)

Cell yields and fermentation responses of a Salmonella Typhimurium poultry isolate at different dilution rates in an anaerobic steady state continuous culture - Kingsley D. Dunkley; Todd R. Callaway; Corliss O’Bryan; Megan M. Kundinger; Claudia S. Dunkley; Robin C. Anderson; David J. Nisbet; P. G. Crandall; Steven C. Ricke (Antonie van Leeuwenhoek, 2009)

Two Cultures of Conservation - Brendan Fisher; Katharine Bolt; Richard B. Bradbury; Toby A. Gardner; Jonathan M.H. Green; David G. Hole; Robin Naidoo (Conservation Biology, 2009)

Birth and Death of Genes and Functions in the β-Esterase Cluster of Drosophila - Charles Robin; Lisa M. J. Bardsley; Chris Coppin; John G. Oakeshott (Journal of Molecular Evolution, 2009)

TMS disruption of V5/MT+ indicates a role for the dorsal stream in word recognition - Robin Laycock; David P. Crewther; Paul B. Fitzgerald; Sheila G. Crewther (Experimental Brain Research, 2009)

Comparison of genetic and cytogenetic maps of hexaploid wheat (Triticum aestivum L.) using SSR and DArT markers - Michael G. Francki; Esther Walker; Allison C. Crawford; Sue Broughton; Herbert W. Ohm; Iain Barclay; Robin E. Wilson; Robyn McLean (Molecular Genetics and Genomics, 2009)

Evaluation of distributed recharge in an upland semi-arid karst system: the West Bank Mountain Aquifer, Middle East - A. G. Hughes; M. M. Mansour; N. S. Robins (Hydrogeology Journal, 2008)

Reproductive strategy of an invasive thistle: effects of adults on seedling survival - Robin G. Marushia; Jodie S. Holt (Biological Invasions, 2008)

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Recombination Rate and AT-content Show Opposite Correlations in Mammalian and Other Animal Genomes - H. Michael G. Lattorff; Robin F. A. Moritz (Evolutionary Biology, 2008)

Linkage to chromosome 2q36.1 in autosomal dominant Dandy-Walker malformation with occipital cephalocele and evidence for genetic heterogeneity - Ali Jalali; Kimberly A. Aldinger; Ajit Chary; David G. Mclone; Robin M. Bowman; Luan Cong Le; Phillip Jardine; Ruth Newbury-Ecob; Andrew Mallick; Nadereh Jafari; Eric J. Russell; John Curran; et al. (Human Genetics, 2008)

Integrating Agricultural Landscapes with Biodiversity Conservation in the Mesoamerican Hotspot - CELIA A. HARVEY; OLIVER KOMAR; ROBIN CHAZDON; BRUCE G. FERGUSON; BRYAN FINEGAN; DANIEL M. GRIFFITH; MIGUEL MARTÍNEZ‐RAMOS; HELDA MORALES; RONALD NIGH; LORENA SOTO‐PINTO; MICHIEL VAN BREUGEL; MARK WISHNIE (Conservation Biology, 2008)

Pacific Salmon Extinctions: Quantifying Lost and Remaining Diversity - RICHARD G. GUSTAFSON; ROBIN S. WAPLES; JAMES M. MYERS; LAURIE A. WEITKAMP; GREGORY J. BRYANT; ORLAY W. JOHNSON; JEFFREY J. HARD (Conservation Biology, 2007)
Widespread population extirpations and the consequent loss of ecological, genetic, and life‐history diversity can lead to extinction of evolutionarily significant units (ESUs) and species. We attempted to systematically enumerate extinct Pacific salmon populations and characterize lost ecological, life history, and genetic diversity types among six species of Pacific salmon (Chinook [ Oncorhynchus tshawytscha ], sockeye [ O . nerka ], coho [ O . kisutch ], chum [ O . keta ], and pink salmon [ O. gorbuscha ] and steelhead trout [ O. mykiss ]) from the western contiguous United States. We estimated that, collectively, 29% of nearly 1400 historical populations of these six species have been lost from the Pacific Northwest and California since Euro‐American contact. Across all species there was a highly significant difference in the proportion of population extinctions between coastal (0.14 extinct) and interior (0.55 extinct) regions. Sockeye salmon (which typically rely on lacustrine habitats for rearing) and stream‐maturing Chinook salmon (which stay in freshwater for many months prior to spawning) had significantly higher proportional population losses than other species and maturation types. Aggregate losses of major ecological, life‐history, and genetic biodiversity components across all species were estimated at 33%, 15%, and 27%, respectively. Collectively, we believe these population extirpations represent a loss of between 16% and 30% of all historical ESUs in the study area. On the other hand, over two‐thirds of historical Pacific salmon populations in this area persist, and considerable diversity remains at all scales. Because over one‐third of the remaining populations belong to threatened or endangered species listed under the U.S. Endangered Species Act, it is apparent that a critical juncture has been reached in efforts to preserve what remains of Pacific salmon diversity. It is also evident that persistence of existing, and evolution of future, diversity will depend on the ability of Pacific salmon to adapt to anthropogenically altered habitats.

Improving fluorometry as a source tracking method to detect human fecal contamination - Peter G. Hartel; Jennifer L. McDonald; Lisa C. Gentit; Sarah N. J. Hemmings; Karen Rodgers; Katy A. Smith; Carolyn N. Belcher; Robin L. Kuntz; Yaritza Rivera-Torres; Ernesto Otero; Eduardo C. Schröder (Estuaries and Coasts, 2007)

Relationships between ericaceous vegetation and soil nutrient status in a post-fire Kalmia angustifolia-black spruce chronosequence - Robin G. Bloom; Azim U. Mallik (Plant and Soil, 2006)

A maternal hypomethylation syndrome presenting as transient neonatal diabetes mellitus - D. J. G. Mackay; S. E. Boonen; J. Clayton-Smith; J. Goodship; J. M. D. Hahnemann; S. G. Kant; P. R. Njølstad; N. H. Robin; D. O. Robinson; R. Siebert; J. P. H. Shield; H. E. White; et al. (Human Genetics, 2006)

The Effects of Habitat on Dispersal Patterns of an Invasive Thistle, Cynara Cardunculus - Robin G. Marushia; Jodie S. Holt (Biological Invasions, 2006)

Seagrass biodiversity of the Fiji and Samoa islands, South Pacific - Posa A. Skelton; G. Robin South (New Zealand Journal of Marine and Freshwater Research, 2006)
Five seagrass species and one subspecies distributed in two families (Hydrocharitaceae and Cymodoceaceae) are reported from the Fiji Islands and the Samoan Archipelago. The Fijian seagrass flora comprises Halophila decipiens, H. ovalis, H. ovalis subspecies bullosa, Halodule pinifolia, Halodule uninervis, and Syringodium isoetifolium. Halophila ovalis, H. ovalis ssp. bullosa, and S. isoetifolium are the only taxa recorded from Samoa. Records of Thalassia hemprichii, Cymodocea serrulata, Halophila minor, and Halophila ovata credited to Fiji and Samoa are either erroneous or remain to be verified. All the species reported herein have an Indo‐Pacific distribution, except H. ovalis ssp. bullosa endemic to Fiji, Tonga, and Samoa. Halophila decipiens is confirmed for the first time from Fiji with all specimens collected subtidally from 10–25 m depth.

Using Niche‐Based Models to Improve the Sampling of Rare Species - ANTOINE GUISAN; OLIVIER BROENNIMANN; ROBIN ENGLER; MATHIAS VUST; NIGEL G. YOCCOZ; ANTHONY LEHMANN; NIKLAUS E. ZIMMERMANN (Conservation Biology, 2006)
Because data on rare species usually are sparse, it is important to have efficient ways to sample additional data. Traditional sampling approaches are of limited value for rare species because a very large proportion of randomly chosen sampling sites are unlikely to shelter the species. For these species, spatial predictions from niche‐based distribution models can be used to stratify the sampling and increase sampling efficiency. New data sampled are then used to improve the initial model. Applying this approach repeatedly is an adaptive process that may allow increasing the number of new occurrences found. We illustrate the approach with a case study of a rare and endangered plant species in Switzerland and a simulation experiment. Our field survey confirmed that the method helps in the discovery of new populations of the target species in remote areas where the predicted habitat suitability is high. In our simulations the model‐based approach provided a significant improvement (by a factor of 1.8 to 4 times, depending on the measure) over simple random sampling. In terms of cost this approach may save up to 70% of the time spent in the field.

Protecting Rare, Old‐Growth, Forest‐Associated Species under the Survey and Manage Program Guidelines of the Northwest Forest Plan - RANDY MOLINA; BRUCE G. MARCOT; ROBIN LESHER (Conservation Biology, 2006)
The Survey and Manage Program of the Northwest Forest Plan (NWFP) represents an unparalleled attempt to protect rare, little‐known species associated with late‐successional and old‐growth forests on more than 9.7 million ha of federal lands. Approximately 400 species of amphibians, bryophytes, fungi, lichens, mollusks, vascular plants, arthropod functional groups, and one mammal were listed under this program because viability evaluations indicated the plan's network of reserve land allocations might not sustain the species over time. The program's standards and guidelines used an adaptive approach, protecting known sites and collecting new information to address concerns for species persistence and to develop management strategies. Since implementation in 1994, approximately 68,000 known sites have been recorded at an expense of several tens of millions of dollars. New knowledge from surveys reduced concern for nearly 100 species, and they were removed from the protection list. Although successful in protecting hundreds of rare species not typically considered in most conservation programs, some of the enacted conservation measures created conflicts in meeting other management objectives of the plan, particularly timber harvest. The program accrued important gains in knowledge, reduced uncertainty about conservation of a number of species, and developed new methods of species inventory that will be useful in future management planning and implementation at many scales. The program, however, was not completed because of changes in land‐management philosophy. Ongoing litigation regarding its termination and potential changes to the plan cast further uncertainty on how the original goal of maintaining persistence of late‐successional and old‐growth species will be met and measured. The outcomes, controversies, and management frustrations of the program exemplify the inherent difficulties in balancing broad, regional conservation goals with social and economic goals of the NWFP. Defining acceptable trade‐offs to reach that balance and developing practical conservation solutions remain challenges for the science and management communities. Lessons learned from the program provide a valuable biological and managerial reference to benefit future discussion on meeting those challenges.

Evidence of the domestication history of flax (Linum usitatissimum L.) from genetic diversity of the sad2 locus - Robin G. Allaby; Gregory W. Peterson; David Andrew Merriwether; Yong-Bi Fu (Theoretical and Applied Genetics, 2005)

Rare royal families in honeybees, Apis melliferas - Robin F. A. Moritz; H. Michael; G. Lattorff; Peter Neumann; F. Bernhard Kraus; Sarah E. Radloff; H. Randall Hepburn (The Science of Nature, 2005)

Rare royal families in honeybees, Apis mellifera - Robin F. A. Moritz; H. Michael G. Lattorff; Peter Neumann; F. Bernhard Kraus; Sarah E. Radloff; H. Randall Hepburn (The Science of Nature, 2005)

Remote sensing of heterogeneity in photosynthetic efficiency, electron transport and dissipation of excess light in Populus deltoides stands under ambient and elevated CO 2 concentrations, and in a tropical forest canopy, using a new laser‐induced fluorescence transient device - Gennady Ananyev; Zbigniew S. Kolber; Dennis Klimov; Paul G. Falkowski; Joseph A. Berry; Uwe Rascher; Robin Martin; Barry Osmond (Global Change Biology, 2005)
Determining the spatial and temporal diversity of photosynthetic processes in forest canopies presents a challenge to the evaluation of biological feedbacks needed for improvement of carbon and climate models. Limited access with portable instrumentation, especially in the outer canopy, makes remote sensing of these processes a priority in experimental ecosystem and climate change research. Here, we describe the application of a new, active, chlorophyll fluorescence measurement system for remote sensing of light use efficiency, based on analysis of laser‐induced fluorescence transients (LIFT). We used mature stands of Populus grown at ambient (380 ppm) and elevated CO 2 (1220 ppm) in the enclosed agriforests of the Biosphere 2 Laboratory (B2L) to compare parameters of photosynthetic efficiency, photosynthetic electron transport, and dissipation of excess light measured by LIFT and by standard on‐the‐leaf saturating flash methods using a commercially available pulse‐modulated chlorophyll fluorescence instrument (Mini‐PAM). We also used LIFT to observe the diel courses of these parameters in leaves of two tropical forest dominants, Inga and Pterocarpus , growing in the enclosed model tropical forest of B2L. Midcanopy leaves of both trees showed the expected relationships among chlorophyll fluorescence‐derived photosynthetic parameters in response to sun exposure, but, unusually, both displayed an afternoon increase in nonphotochemical quenching in the shade, which was ascribed to reversible inhibition of photosynthesis at high leaf temperatures in the enclosed canopy. Inga generally showed higher rates of photosynthetic electron transport, but greater afternoon reduction in photosynthetic efficiency. The potential for estimation of the contribution of outer canopy photosynthesis to forest CO 2 assimilation, and assessment of its response to environmental stress using remote sensing devices such as LIFT, is briefly discussed.

Differential respirable dust related lung function effects between current and former South African coal miners - Rajen N. Naidoo; Thomas G. Robins; Noah Seixas; Umesh G. Lalloo; Margaret Becklake (International Archives of Occupational and Environmental Health, 2005)

A comparison of wind-tunnel experiments and numerical simulations of neutral and stratified flow over a hill - A.N. Ross; S. Arnold; S.B. Vosper; S. D. Mobbs; N. Dixon; A. G. Robins (Boundary-Layer Meteorology, 2004)

Radiographic outcomes among South African coal miners - Rajen N. Naidoo; Thomas G. Robins; A. Solomon; Neil White; Alfred Franzblau (International Archives of Occupational and Environmental Health, 2004)

Indirect effects of black spruce (Picea mariana) cover on community structure and function in sheep laurel (Kalmia angustifolia) dominated heath of eastern Canada - Robin G. Bloom; Azim U. Mallik (Plant and Soil, 2004)

Viable Transgenic Goats Derived from Skin Cells - Esmail Behboodi; Erdogan Memili; David T. Melican; Margaret M. Destrempes; Susan A. Overton; Jennifer L. Williams; Peter A. Flanagan; Robin E. Butler; Hetty Liem; Li How Chen; Harry M. Meade; William G. Gavin; et al. (Transgenic Research, 2004)

Large-Eddy Simulation of Turbulent Flow Over a Rough Surface - Zhengtong Xie; Peter R. Voke; Paul Hayden; Alan G. Robins (Boundary-Layer Meteorology, 2004)

Deep New Zealand. Blue water, black abyss. By PeterBatson. Published in 2003 by Canterbury University Press, Christchurch, New Zealand. 240 p. Softcover. ISBN 1–877257–09–5 Price: NZ#DL49.95.The living reef: the ecology of New Zealand's rocky reefs. Edited by NeilAndrew and MalcolmFrancis. Published in 2003 by Craig Potton Publishing, P.O. Box 555, Nelson, New Zealand (http//www.craigpotton.co.nz). 283 p., hardcover. ISBN: 1–877333–02–6. Price: NZ$59.95 (orders: info@cpp.co.nz).River mechanics. By Pierre Y.Julien. Published in 2002 by Cambridge University Press, Shaftesbury Road, Cambridge, CB2 2RU, United Kingdom (http://uk.cambridge.org/). 454 p., hardback (ISBN: 0521562848) and softback (ISBN: 0521529700). Price: £80.00 (hardback); £33.00 (softback) (orders: directcustserve@cambridge.org). - G. Robin South; Russell Millar; Graeme Smart (New Zealand Journal of Marine and Freshwater Research, 2004)

Acclimation of Arabidopsis thaliana to the light environment: the relationship between photosynthetic function and chloroplast composition - Shaun Bailey; Peter Horton; Robin G. Walters (Planta, 2004)

Is it possible to mitigate greenhouse gas emissions in pastoral ecosystems of the tropics? - Robin S. Reid; Philip K. Thornton; Graeme J. McCrabb; Russell L. Kruska; Fred Atieno; Peter G. Jones (Environment, Development and Sustainability, 2004)

Allelic variation at alcohol metabolism genes ( ADH1B , ADH1C , ALDH2 ) and alcohol dependence in an American Indian population - Connie J. Mulligan; Robert W. Robin; Michael V. Osier; Nyamkhishig Sambuughin; Lev G. Goldfarb; Rick A. Kittles; Diane Hesselbrock; David Goldman; Jeffrey C. Long (Human Genetics, 2003)

South Pacific reef plants. A divers’ guide to the plant life of South Pacific coral reefs. By Diane ScullionLittler and Mark MastertonLittler. Published in February 2003 by OffShore Graphics Inc., Washington, D.C., United States. 331 p. ISBN: 0–9678901–9‐5. Price: US$45.00. - G. Robin South (New Zealand Journal of Marine and Freshwater Research, 2003)

Disruption of exon definition produces a dominant-negative growth hormone isoform that causes somatotroph death and IGHD II - Robin C. C. Ryther; Lindsay M. McGuinness; John A. Phillips; Chanda T. Moseley; Charalambos B. Magoulas; Iain C. A. F. Robinson; James G. Patton (Human Genetics, 2003)

Potential Improvements in the Characterization of Forest Canopy Gaps Caused by Windthrow Using Fine Spatial Resolution Multispectral Data: Comparing Hard and Soft Classification Techniques - Giles M. Foody; Robin G. Jackson; Christopher P. Quine (Forest Science, 2003)
Gaps often form in forest canopies due to windthrow and have important management and ecological implications. Remote sensing has considerable potential for the provision of information on gap properties but this has not been fully realized. This is largely due to the use of conventional (hard, one-pixel one-class) image analysis techniques and imagery with a relatively coarse spatial resolution. This article investigates the potential to extract information on gap properties from fine spatial resolution airborne thematic mapper imagery using soft classification techniques that allow image pixels to have multiple and partial class membership. It is shown that a standard hard maximum likelihood classification may be used to derive an accurate map of the land cover of a forested site (95.1%) from which gaps in a canopy of Sitka spruce were accurately identified (94.5%). The maximum likelihood classification was also softened by outputting probabilities of class membership for each pixel. Softening the classification increased the information on gap properties that could be extracted from the data. In particular, the accuracy with which key gap properties, such as gap area, perimeter length and shape, were estimated was higher in the outputs of the softened than hard classification. Thus, while strong correlations between the remotely sensed and ground data estimates of gap area (r ≥ 0.96) and perimeter (r ≥ 0.87), based on a sample of 36 gaps, were derived from all classifications, the accuracy with which gap properties were estimated was generally highest when a soft classification was used. For example, the use of a soft rather than hard classification resulted in the root mean square error in estimating gap area declining from 144.90 to 132.87 m2. Furthermore, the soft classification allowed the sharpness of the gap boundary to be estimated, enabling further gap properties to be inferred. In particular, the soft classification output enabled the direction of the wind event causing the initial damage to be estimated, and it may aid the definition of sites with a future risk of windthrow. FOR. SCI. 49(3):444–454.

Occurrence and use of Compsopogon coeruleus (Rhodophyta: Compsopogonaceae) in Fiji, South Pacific - G. Robin South; Posa A. Skelton (New Zealand Journal of Marine and Freshwater Research, 2002)
The rhodophyte Compsopogon coeruleus (Balbis ex C. Agardh) Montagne is newly recorded from Fiji, South Pacific. Plants occur in dense masses in the Wainivesi River in the province of Tailevu. Local villagers collect the plants and use them to cook a “pudding” with tinned fish, very similar to “puddings” prepared by coastal Fijians using marine species such as Gracilaria and Hypnea . This is the first documented account of the use of Compsopogon as a gelling agent in the preparation of human food.

Locating genomic regions associated with components of drought resistance in rice: comparative mapping within and across species - J. Zhang; H. G. Zheng; A. Aarti; G. Pantuwan; T. T. Nguyen; J. N. Tripathy; A. K. Sarial; S. Robin; R. C. Babu; Bay D. Nguyen; S. Sarkarung; A. Blum; et al. (Theoretical and Applied Genetics, 2001)

Effects of weather on activity and sleep in brooding king penguins ( Aptenodytes patagonicus ) - Dewasmes G.; Côté S.; Y. Le Maho; Groscolas R.; Robin J.; Vardon G.; Libert J. (Polar Biology, 2001)

Inhibition of prostaglandin synthesis in intact cells by paracetamol (acetaminophen) - Garry G. Graham; Sally-Anne Robins; Katherine J. Bryant; Kieran F. Scott (Inflammopharmacology, 2001)

Elevational distribution of restricted range forest tree taxa in eastern Tanzania - Jon C. Lovett; G. Philip Clarke; Robin Moore; Gilbert H. Morrey (Biodiversity and Conservation, 2001)

Changes in Production and Nutrient Cycling across a Wetness Gradient within a Floodplain Forest - Robin G. Clawson; B. Graeme Lockaby; Bob Rummer (Ecosystems, 2001)

Reconstructing the Diversification of α-Esterases: Comparing the Gene Clusters of Drosophila buzzatii and D. melanogaster - G. Charles de Q. Robin; Charles Claudianos; Robyn J. Russell; John G. Oakeshott (Journal of Molecular Evolution, 2000)

Simulated moderate altitude elevates serum erythropoietin but does not increase reticulocyte production in well-trained runners - Michael J. Ashenden; Christopher J. Gore; Geoffrey P. Dobson; Tanya T. Boston; Robin Parisotto; Kerry R. Emslie; Graham J. Trout; Allan G. Hahn (European Journal of Applied Physiology, 2000)

Control of voluntary and reflexive saccades - Robin Walker; David G. Walker; Masud Husain; Christopher Kennard (Experimental Brain Research, 2000)

Photoenhanced toxicity of a weathered oil onCeriodaphnia dubia reproduction - Robin D. Calfee; Edward E. Little; Laverne Cleveland; Mace G. Barron (Environmental Science and Pollution Research, 1999)

Ethnobotany of Woody Species in Second‐Growth, Old‐Growth, and Selectively Logged Forests of Northeastern Costa Rica - Robin L. Chazdon; Felix G. Coe (Conservation Biology, 1999)
We assessed quantitatively the woody species used for timber, medicine, and other products in 10 tropical wet‐forest stands with different land‐use histories in the Atlantic lowlands of northeastern Costa Rica. Species were classified into 20 use categories based on regional ethnobotanical studies. Three size classes of woody vegetation were sampled in nested, contiguous plots along transects: trees (≥5 cm diameter at breast height [dbh]), saplings (>1 m high, 20 cm high,

Acclimation of Arabidopsis thaliana to the light environment: the role of photoreceptors - Robin G. Walters; Jennifer J. M. Rogers; Freya Shephard; Peter Horton (Planta, 1999)

Stool Water Content and Colonic Drug Absorption: Contrasting Effects of Lactulose and Codeine - John M. Hebden; Peter J. Gilchrist; Alan C. Perkins; Clive G. Wilson; Robin C. Spiller (Pharmaceutical Research, 1999)

Structural and functional heterogeneity in the major light-harvesting complexes of higher plants - Robin G. Walters; Peter Horton (Photosynthesis Research, 1999)

Regional Differences in Quinine Absorption from the Undisturbed Human Colon Assessed Using a Timed Release Delivery System - John M. Hebden; Clive G. Wilson; Robin C. Spiller; Peter J. Gilchrist; Elaine Blackshaw; Malcolm E. Frier; Alan C. Perkins (Pharmaceutical Research, 1999)

Carbomer Inhibits Tryptic Proteolysis of Luteinizing Hormone-Releasing Hormone and N-α-Benzoyl-L-Arginine Ethyl Ester by Binding the Enzyme - Greg F. Walker; Robin Ledger; Ian G. Tucker (Pharmaceutical Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Acceptable practices in Ontario's forests: Differences between the public and forestry professionals - Robert G. Wagner; James Flynn; C.K. Mertz; Paul Slovic; Robin Gregory (New Forests, 1998)

Simulation of Pollution Dispersion Using Small Scale Physical Models - an Assessment of Scaling Options - E D Obasaju; A G Robins (Environmental Monitoring and Assessment, 1998)

Discrete consumers, small scale resource heterogeneity, and population stability - Roger M. Nisbet; Andre M. De Roos; William G. Wilson; Robin E. Snyder (Ecology Letters, 1998)
We present a consumer‐resource model in which individual consumers subsist on a continuum of resource distributed over a very large number of small “bite‐sized” patches, each patch being sufficiently small that all its resource is eaten whenever a consumer visits. This form of consumer–resource interaction forces a heterogeneous distribution of resource among the patches, and may dampen out the large amplitude, consumer‐resource cycles that are predicted by traditional models of well‐mixed, spatially homogeneous systems. The resource equilibrium does not increase with enrichment, a prediction that distinguishes this model from models that invoke direct or indirect consumer density dependence as a stabilizing mechanism.

The effects of elevated light on Photosystem II function: A thermoluminescence study - Robin G. Walters; Giles N. Johnson (Photosynthesis Research, 1997)

How do nutrients drive growth? - Ian G. Burns; Robin L. Walker; Jeff Moorby (Plant and Soil, 1997)

Non-functional CYP2D6 alleles and risk for neuroleptic-induced movement disorders in schizophrenic patients - Ole A. Andreassen; T. MacEwan; Anne-Karin Gulbrandsen; Robin G. McCreadie; V. M. Steen (Psychopharmacology, 1997)

New polyester arterial prostheses from great britain: anin vitro andin vivo evaluation - Robert G. Guidoin; Martin King; Michel Marois; Louisette Martin; Daniel Marceau; Robin Hood; Roshan Maini (Annals of Biomedical Engineering, 1986)

Olpidiopsis antithamnionis n. sp. (Oomycetes, Olpidiopsidaceae), a parasite of Antithamnion floccosum (O. F. Mll.) Kleen from Newfoundland - Alan Whittick; G. Robin South (Archives of Microbiology, 1972)